Nanoreservoir

Nanoreservoirs, like nanogels, attached to medical devices provide enhanced biocompatibility and durability by combining antimicrobial, antibiofilm, antithrombotic, and anticalcification properties, addressing issues in current medical devices by reducing infections and thrombosis.

JP7620390B2Active Publication Date: 2025-01-23ジェスヴァル ソシエテ アノニム
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2019534800
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-12-28
Filing Date
2017-12-28
Publication Date
2025-01-23
Estimated Expiration
2037-12-28

AI Technical Summary

Technical Problem

Current medical devices face challenges with biocompatibility issues, including thrombotic complications, infections, and limited durability, particularly in cardiovascular devices like artificial heart valves, which lack combined antimicrobial, antibiofilm, antithrombotic, and anticalcification properties.

Method used

Development of nanoreservoirs, such as nanogels, that are attached to medical devices and biomaterials, containing bioactive compounds like antibiotics and antiplatelet agents, providing enhanced biocompatibility and durability by reducing infections and thrombosis through controlled release of therapeutic agents.

Benefits of technology

The nanoreservoirs improve the biocompatibility and durability of medical devices by preventing infections and thrombosis, while maintaining functionality, and can be applied to various medical devices including heart valves, stents, and other implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620390000024
    Figure 0007620390000024
  • Figure 0007620390000025
    Figure 0007620390000025
  • Figure 0007620390000026
    Figure 0007620390000026
Patent Text Reader

Abstract

Nanoreservoirs and uses thereof, in particular the use of nanoreservoirs for coating the surface of a medical device, biomaterial or bioprosthesis.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nanoreservoirs, methods for making such nanoreservoirs and their uses, in particular the use of nanoreservoirs suitable for coating medical devices. [Background technology]

[0002] Medical devices and biomaterial implants are used clinically in a variety of applications, and their performance is critical to a patient's overall health and quality of life.

[0003] Most medical devices pose biocompatibility problems. Importantly, the implantation of a foreign body into the vascular system can activate the contact pathway of coagulation, leading to thrombotic complications. In particular, there is a medical need to improve the biocompatibility and durability of prosthetic heart valves, currently one of the most widely used cardiovascular devices. Mechanical prosthetic heart valves are subject to a considerable risk of thromboembolism and thrombotic occlusion and often require chronic anticoagulation therapy, which in turn is associated with an increased risk of hemorrhagic complications. In contrast, bioprosthetic heart valves, despite their low risk of thromboembolism without anticoagulation, are limited in their durability by calcified or noncalcified tissue deterioration.

[0004] Medical devices and biomaterials can also become infected, and treatment of such infections generally requires removal of the entire component / system and administration of antibiotics to target the causative bacteria.

[0005] As highlighted above, there is a need for the creation of antibacterial, antibiofilm, antithrombotic, anti-inflammatory and / or anti-calcification products that can be fixed or attached to the surface of biomaterials or medical devices.

[0006] Previous attempts have been made to modify the surfaces of biomaterials and medical devices to improve the biocompatibility of blood-contacting devices. Surface modification strategies have also been employed to prevent bacterial contamination of biomaterials, such as coating the surfaces of biomaterials and medical devices with silver, which has antibacterial properties. However, none of these surface modifications provide combined properties, such as antibacterial, antibiofilm, antithrombosis, and anticalcification. Summary of the Invention

[0007] The present invention relates to nanoreservoirs, such as nanogels, that provide a larger cargo space that can be used to incorporate bioactive compounds. Such nanoreservoirs can be fixed or attached onto the surface of any biomaterial or medical device, whether metallic or polymeric or bioprosthetic, thereby helping to reduce or prevent infection and improve the biocompatibility and hemocompatibility of temporarily or permanently implanted materials to maintain their functionality and increase their durability. Although overlapping with other descriptions, one embodiment of the present invention will be described below. However, the present invention is not limited to the following. [1] A nanoreservoir comprising nanoparticles of a nanogel, the nanogel being crosslinked to a second polymer comprising a hydrophilic backbone and one or more reactive moieties, the ... hydrophilic backbone being represented by Formula I: [C1] JPEG0007620390000001.jpg60154 wherein the nanoreservoir further comprises one or more bioactive molecules, therapeutic molecules or drugs. [2] A biomaterial implant, medical device or bioprosthesis, the surface of which or a part thereof is coated with the nanoreservoirs described in [1]. [3] The nanoreservoir of [1] or the biomaterial implant, medical device or bioprosthesis of [2], wherein the nanoreservoir contains an antibiotic and / or an antiplatelet agent. [4] The nanoreservoir or biomaterial implant, medical device or bioprosthesis according to any of [1] to [3], wherein the hydrophilic polymer or copolymer backbone may comprise one or more of polyallylamine, polyvinylamine, polyvinylamide, polyvinyl alcohol, poly(meth)acrylate, poly(meth)acrylamide, polyurethane or PEG or polyelectrolytes (cationic, anionic or zwitterionic) or hydrophilic biopolymers (e.g. polysaccharides such as chitosan or hyaluronan). [5] The nanoreservoir or biomaterial implant, medical device or bioprosthesis according to any one of [1] to [4], wherein the first polymer is P(mPOPA). [6] The nanoreservoir or biomaterial implant, medical device or bioprosthesis according to any one of [1] to [5], wherein the second polymer is poly(allylamine hydrochloride). [7] The nanoreservoir or biomaterial implant, medical device or bioprosthesis described in any of [1] to [6], wherein the nanoparticles have a diameter of 100 nm to 250 nm. [8] The nanoreservoir or biomaterial implant, medical device or bioprosthesis described in any of [1] to [7], wherein at least some of the nanoparticles are decorated with hydrophilic functionalizing ligands. [9] The nanoreservoir or biomaterial implant, medical device or bioprosthesis of [8], wherein the hydrophilic functionalized ligand is a thiol or vinyl end-functionalized ligand.

[10] The nanoreservoir or biomaterial implant, medical device or bioprosthesis according to [9], wherein the hydrophilic functionalizing ligand is PEG2, or a PEG having a molecular weight greater than 2000.

[11] The nanoreservoir or biomaterial implant, medical device or bioprosthesis described in any of [1] to

[10] , wherein the nanoreservoir comprises two or more nanoparticle layers.

[12] The biomaterial implant, medical device or bioprosthesis described in any one of [1] to

[11] , wherein the bioprosthesis is a heart valve.

[13] A method for making a nanoreservoir containing at least two biologically active molecules, therapeutic molecules or drugs, said method comprising: i) mixing Pox(mDOPA) in an aqueous solution with one biologically active molecule, therapeutic molecule or drug; ii) adding a PAH solution to the resulting aqueous solution of Pox(mDOPA) obtained in step i) to form a first nanogel solution; iii) repeating steps i) and ii) with a second bioactive molecule, therapeutic molecule or drug to form a second nanogel solution; iv) mixing said first and second nanogel solutions to obtain nanoreservoirs carrying two bioactive molecules, therapeutic molecules or drugs; A method comprising:

[14] 1. A method for producing a medical device, biomaterial implant or bioprosthesis having a coated surface, comprising: i) immersing the surface to be coated in a solution of a first polymer, said first polymer having formula I: [C2] JPEG0007620390000002.jpg60153 and ii) oxidizing the first polymer; iii) immersing the resulting surface in a solution of a second polymer, said second polymer comprising a hydrophilic backbone and one or more reactive moieties; iv) immersing the surface in a nanoreservoir solution containing nanoparticles of nanogel to produce a coating on the surface, the nanogel being a polymer having the formula I: [C3] JPEG0007620390000003.jpg60154 and v) optionally immersing the coated surface in a solution of a hydrophilic functionalizing ligand; A method comprising:

[15] The method according to

[14] , wherein the nanoreservoir in step iv) is as defined in any one of [1] and [3] to

[10] .

[16] The method according to

[14] , wherein in step i) the first polymer is P(mDOPA), and / or in step ii) the oxidized polymer is Pox(mDOPA), and / or in step iii) the second polymer is PAH, and in step iv) the nanoreservoir comprises nanoparticles of crosslinked Pox(mDOPA) and PAH, and optionally: [C4] JPEG0007620390000004.jpg9541 and / or in step v) said hydrophilic functionalized ligand is PEG2 or a PEG with a MW greater than 2000.

[0008] According to a first aspect of the present invention, there is provided a nanoreservoir comprising a first polymer and a second polymer, the first polymer having one or more catechol moieties and the second polymer comprising a hydrophilic backbone having one or more reactive moieties.

[0009] Nanoreservoirs can refer to nanoparticles that preferably include nanogels, which are composed of hydrogels with cross-linked hydrophilic polymer networks. Nanogels are most often composed of synthetic or biopolymers that are chemically or physically cross-linked. The pores in nanogels can be filled with small molecules or macromolecules, and their properties (such as swelling, degradation, and chemical functionality) can be controlled.

[0010] In one embodiment of the invention, the nanoreservoirs comprise nanoparticles formed from nanogels. A nanoparticle is any particle having a longest dimension less than 1000 nm (e.g., about 10 nm to 300 nm). For example, the nanoreservoirs can have a longest dimension less than about 500 nm, less than about 300 nm, less than about 200 nm, less than about 150 nm, less than about 100 nm, less than about 50 nm, less than about 30 nm, less than about 10 nm, or less than about 3 nm. In certain embodiments, the nanoreservoirs of the invention comprise nanoparticles having a diameter of about 150 nm to about 250 nm. In certain embodiments, the nanoreservoirs of the invention comprise nanoparticles having a diameter of about 100 to about 250 nm.

[0011] Preferably, the nanoparticles in the nanoreservoirs of the present invention are made of a first and a second polymer, which may be crosslinked.

[0012] The crosslinking between the first and second polymers may involve an amine-quinone reaction. Preferably, the crosslinking does not use radical polymerization.

[0013] The first polymer has Formula 1: [ka] It may have a structure as defined in

[0014] The catechol moiety can have the following structure, also known as benzene 1,2 diol: [ka]

[0015] The linker can be an alkyl ester, N-alkyl amide, alkyl, or alkoxy group.

[0016] The hydrophilic polymer or copolymer backbone may comprise one or more of polyallylamine, polyvinylamine, polyvinylamide, polyvinyl alcohol, poly(meth)acrylate, poly(meth)acrylamide, polyurethane or PEG or polyelectrolytes (cationic, anionic or zwitterionic) or hydrophilic biopolymers (e.g. polysaccharides such as chitosan or hyaluronan).

[0017] The first polymer can be polyDOPA, for example poly(N-methacryloyl 3,4-dihydroxy-L-phenylalanine methyl ester), also referred to as P(mDOPA), as shown below. [ka]

[0018] Prior to use, P(mDOPA) can be oxidized to form Pox(mDOPA) as shown below. [ka]

[0019] The first polymer can be P(mDOPA), or polyDOPA, or a copolymer thereof with a hydrophilic monomer (cationic, anionic, zwitterionic, or neutral water-soluble monomer). In a preferred embodiment, the first polymer is a P(mDOPA) copolymer.

[0020] In the second polymer, the hydrophilic backbone may comprise one or more of polyallylamine, polyvinylamine, polyvinylamide, polyvinyl alcohol, poly(meth)acrylate, poly(meth)acrylamide, polyurethane, polyethylene glycol (PEG), polyelectrolytes (cationic, anionic or zwitterionic) with reactive groups such as primary or secondary amines or thiols, or hydrophilic biopolymers (e.g. polysaccharides such as chitosan or hyaluronan).

[0021] The reactive moiety can be a primary or secondary amine or a thiol.

[0022] The second polymer may be a natural or synthetic polymer having primary amine functional groups, such as polyvinylamine, chitosan, or a protein. In a preferred embodiment, the second polymer may comprise a polyallylamine, such as poly(allylamine hydrochloride), also known as PAH, as shown below. [ka]

[0023] In a preferred embodiment, the nanoreservoir comprises nanoparticles formed from cross-linked P(mDOPA) and PAH, which contain one or both of the following bonds: [ka]

[0024] In a preferred embodiment, the nanoreservoirs contain one or more bioactive molecules, therapeutic molecules or drugs in addition to nanoparticles of crosslinked first and second polymers.

[0025] The nanoreservoirs may be loaded with one or more bioactive agents, such as bioactive molecules, therapeutic molecules, or drugs, including antibiotics, anti-biofilm agents, antiplatelet agents, anticoagulants, antithrombotic agents, and anticalcification agents. The bioactive agents may be located within nanoparticles within the nanoreservoirs and / or between nanoparticles within the nanoreservoirs.

[0026] Bioactive agents can include any agent that is desired to be delivered to a molecule, cell, tissue, or organ to modulate or alter molecular or cellular function, such as for a therapeutic effect. Bioactive agents include, but are not limited to, pharma- ceutical active compounds or diagnostic compounds.Biologically active compounds include, but are not limited to, nucleotides (aptamers, RNAi, antisense oligonucleotides), peptides, oligopeptides, proteins, apoproteins, glycoproteins, antigens and their antibodies or antibody fragments, receptors and other membrane proteins, retro-inverso oligopeptides, protein analogs in which at least one non-peptide bond replaces a peptide bond, enzymes, coenzymes, enzyme inhibitors, amino acids and their derivatives, hormones, lipids, phospholipids, liposomes, ricin or ricin fragments; toxins such as aflatoxin, digoxin, xanthotoxin, rubratoxin; analgesics such as aspirin, ibuprofen, acetaminophen; bronchodilators such as theophylline, albuterol; beta blockers such as propranolol, metoprolol, atenolol, labetolol, timolol, penbutolol, pindolol; the above as well as antibacterial agents such as ciprofloxacin, cinoxacin and norfloxacin; clonidine, methyldopa, antihypertensives, such as prazosin, verapamil, nifedipine, aptopril, and enalapril; cardiovascular drugs, including antiarrhythmics, cardiac glycosides, antianginals, and vasodilators; central nervous system drugs, including stimulants, psychotropic drugs, antimanic drugs, and antidepressants; antiviral drugs; antihistamines, such as chlorpheniramine and brompheniramine; anticancer drugs, including chlorambucil, carboplatin, busulfan derivatives, and chemotherapy agents such as doxorubicin, etoposide, and topotecan (TPT); diazepam, chordiazepoxide (chordiaz epoxide), tranquilizers such as oxazepam, alprazolam, triazolam; antidepressants such as fluoxetine, amitriptyline, nortriptyline, imipramine; H-2 antagonists such as nizatidine, cimetidine, famotidine, ranitidine; anticonvulsants; antiemetics; prostaglandins; muscle relaxants; anti-inflammatory substances; stimulants; decongestants; antiemetics; diuretics; antispasmodics; antiasthmatics; antiparkinsonians; expectorants; cough suppressants; mucolytics; vitamins, minerals and nutritional additives.Other molecules include nucleotides; oligonucleotides; polynucleotides; their art-recognized biologically functional analogs and derivatives, including, for example, methylated polynucleotides, nucleotide analogs having phosphorothioate linkages; plasmids, cosmids, artificial chromosomes, and other nucleic acid vectors; antisense polynucleotides, including those that are substantially complementary to at least one endogenous nucleic acid or have a sequence that is opposite in meaning to at least a portion of a selected viral or retroviral genome; promoters; enhancers; inhibitors; and other ligands for regulating gene transcription and translation.

[0027] The bioactive agent can be an anti-infective agent, including, but not limited to, antibiotics such as amikacin, gentamicin, kanamycin, neomycin, netilmicin, tobramycin, paromomycin, streptomycin, spectinomycin, geldanamycin, herbimycin, rifaximin, loracarbef, ertapenem, dorpenem, imipenem / cilastatin, meropenem, cefadroxil, cefazolin, cephalothin, cephalexin, cefaclor, cefamandole, cefoxitin, cefproxil (cefp roxil), cefuroxime, cefixime, cefdinir, cedophytren, cefoperazone, cefotaxime, cefpodoxime, ceftazidime, ceftibuten, ceftizoxime, ceftriaxone, cefepime, ceftaroline fosamil, ceftobiprole, teicoplanin, vancomycin, telavancin, daibavancin, oritavancin, clindamycin, lincomycin, daptomycin, azithromycin, clarithromycin, dirithromycin, erythromycin, roxithromycin, toxo Loreandomycin, telithromycin, spiramycin, aztreonam, furazolidone, nitrofurantoin, linezolid, amoxicillin, ampicillin, piperacillin, ticarcillin, bacitracin, colistin, polymyxin B, ciprofloxacin, enoxacin, gatifloxacin, gemifloxacin, levofloxacin, lomefloxacin, moxifloxacin, nalidixic acid, norfloxacin, ofloxacin, mafenide, sulfacetamide, sulfadiazine, silver sulfadiazine, sulfadimethoxine, sulphadiazine, sulphadimethoxine ... These include sulfamethizole, sulfamethoxazole, sulfanilimide, sulfisoxazole, trimethoprim-sulfamethoxazole, sulfonamide chrysoidine, demeclocyline, doxycycline, minocycline, oxytetracycline, tetracycline, clofazimine, dapsone, rifampicin, rifabutin, arspenamine, chloramphenicol, fosfomycin, metronidazole, thiamphenicol, tigecycline, tinidazole, and trimethoprim.

[0028] Anti-biofilm agents include, but are not limited to, natural peptides such as the human cathelicidin LL-37 or the bovine peptide indolicidin, or synthetic peptides such as 1018, natural compounds with a 2-aminoimidazole moiety, 2-aminoimidazole inhibitors, benzimidazole analogues, indole-triazo-amide analogues, plant-derived biofilm inhibitors such as emodin, phloretin, casbane diterpenes, resveratrol and its oligomers, sulfur derivatives, brominated furanone analogues, bromopyrrole alkaloids, skyramycin and (-)-ageloxime D structures, cembranoids, N-acyl homoserine lactone analogues, carolactones, molecules that disrupt the formation of amyloid-like fibers, fatty acids, nitric oxide donors, ionic liquids such as 1-alkyl-3-methylimidazolium chlorides, 1-alkylquinolinium bromides, all of which may be used in combination with traditional antibiotics.

[0029] Antiplatelet agents include, but are not limited to, irreversible cyclooxygenase inhibitors such as aspirin and triflusal (Disgren), adenosine diphosphate (ADP) receptor inhibitors such as clopidogrel (Plavix), prasugrel (Effient), ticagrelor (Brilinta), ticlopidine (Ticlid), phosphodiesterase inhibitors such as cilostazol (Pletal), protease-activated receptor-1 (PAR-1) inhibitors such as vorapaxar (Zontivity), and valproate (Ventilator). These include glycoprotein IIB / IIIA inhibitors (intravenous use only) such as abciximab (ReoPro), eptifibatide (Integrilin), tirofiban (Aggrastat), adenosine reuptake inhibitors such as dipyridamole (Persantine), thromboxane synthase inhibitors, thromboxane receptor antagonists such as terutroban, glycoprotein VI inhibitors such as Revacept, glycoprotein Ib inhibitors, and von Willebrand factor inhibitors.

[0030] Anticoagulants include, but are not limited to, acenocoumarol, coumatetralyl, dicoumarol, ethyl biscoumarate, phenprocoumon, warfarin, chlorindione, diphenadione, phenindione, cyclomalol, bemiparin, certoparin, ardeparin, dalteparin, enoxaparin, nadroparin, parnaparin, reviparin, dabigatran, apixaban, betrixaban, darexaban, edoxaban, otamixaban, rivaroxaban, alteplase, danaparoid, tinzaparin, and fondaparinux.

[0031] Thrombolytic agents include, but are not limited to, alteplase, reteplase, tenecteplase, saruplase, urokinase, anistreplase, monteplase, streptokinase, ancrod, brinase, and fibrinolysin.

[0032] Anti-calcification agents include, but are not limited to, bisphosphonates, aluminum salts, glutaraldehyde, aminooleic acid, and metalloproteinase inhibitors.

[0033] In a preferred embodiment, the nanoreservoir of the present invention comprises nanoparticles of crosslinked first and second polymers and at least one, preferably at least two, bioactive molecules, therapeutic molecules and / or drugs. The nanoreservoir may contain an antiplatelet agent and / or an antibiotic. The bioactive molecules, therapeutic molecules or drugs may be encapsulated within the nanoparticles and / or covalently bound to reactive moieties of the nanoparticles.

[0034] The nanoreservoir may contain an antibiotic and an antiplatelet agent in a ratio of about 1 part antibiotic to about 5 parts antiplatelet agent, or about 2 parts antibiotic to about 3 parts antiplatelet agent.

[0035] In further embodiments, hydrophilic functionalized ligands may be grafted onto the assembled crosslinked nanogel nanoparticles. The hydrophilic ligands may include thiol or vinyl end functionalized ligands. The functionalized ligands may include one or more PEG (polyethylene glycol) molecules and / or one or more vinyl end functionalized PEG ligands, such as PEG-acrylate molecules. When PEG is used, the PEG may be PEG1.5 (methoxy-PEG-(CH2)2-SH, Mw 2,000), PEG2 (methoxy-PEG-(CH2)2-SH, Mw 2,000), PEG5 (methoxy-PEG-(CH2)2-SH, Mw 5,000) or PEG10 (methoxy-PEG-(CH2)2-SH, Mw 10,000). When PEG-acrylate (APEG) is used, the molecule can be APEG (polyethylene glycol methyl ether acrylate, Mw 480) or APEG1 (polyethylene glycol methyl ether acrylate, MW 1,000). The functionalizing ligand can also include polybetaine. In a preferred embodiment, at least PEG2, or PEG with a higher molecular weight, is used as the functionalizing ligand.

[0036] Nanoreservoirs containing nanoparticles with hydrophilic ligands preferably exhibit anti-adhesive properties against platelets and bacteria when compared to nanogel nanoparticles that do not contain hydrophilic ligands.

[0037] Preferably, the hydrophilic ligands are added after the formation of the nanogel nanoparticles and are attached onto the nanoparticle surface.

[0038] Thus, the present invention provides a nanoreservoir comprising nanoparticles comprising a first polymer and a second polymer, wherein the first polymer having one or more catechol moieties is crosslinked to a second polymer comprising a hydrophilic backbone having one or more reactive moieties, and the nanoparticles are surface decorated with hydrophilic ligands.

[0039] According to another aspect, the present invention provides a nanoreservoir comprising two or more layers of nanogel. Each layer of nanogel may comprise nanoparticles as described herein. Each layer may be the same or different. For example, one layer may comprise a bioactive agent. One layer may comprise nanogels loaded with different bioactive molecules. Alternatively, different layers may comprise different bioactive agents. The nanoreservoir may comprise two, three, four, five or more layers of nanogel nanoparticles. By using a multi-layered nanoreservoir, the antithrombotic and / or antibiofilm properties of the nanoreservoir may be improved. The presence of multiple layers of nanogel may prolong the release of the bioactive agent from within the nanoreservoir.

[0040] In a preferred embodiment, the nanoreservoir of the present invention comprises at least 5 layers of nanogel nanoparticles, at least the top layer of nanoparticles has functionalized ligands. The nanoreservoir can comprise at least 2, 3, 4, 5 or more layers, where at least 1, 2, 3, 4 or 5 layers contain bioactive molecules, therapeutic molecules or drugs, such as antibacterial agents and / or anti-platelet agents, and have functionalized ligands in their top layers. The antibacterial agent can be minocycline. The antiplatelet agent can be ticagrelor. The functionalized ligand can be PEG2 or a PEG molecule with a MW of about 2000 or more.

[0041] The nanoreservoirs of the present invention may have antibacterial and / or antithrombotic / antiplatelet properties imparted by the bioactive agents incorporated into the nanoreservoirs and / or as a result of the chemical composition used to fabricate the nanoparticles.

[0042] In a further aspect of the invention, the nanoreservoirs of the invention can be used as coatings, for example to coat the surfaces of biomaterial implants, medical devices or bioprostheses.

[0043] In a still further aspect, the present invention provides a biomaterial implant, medical device or bioprosthesis, at least a part of whose surface is coated with nanoreservoirs according to the present invention.

[0044] The biomaterial implant may be an implantable foreign body for clinical use in a host mammal, such as artificial joints, pacemakers, implantable cardioverter defibrillators, catheters or materials including intravascular or urinary catheters, stents including coronary stents, mechanical and biological artificial heart valves, intraocular lenses, dental implants, etc. In a preferred embodiment, the biomaterial implant is a bioprosthesis.

[0045] A medical device includes, but is not limited to, any apparatus, tool, instrument, implant, etc., associated with medicine or human or veterinary practice, or intended for use to cure or treat a disease or condition. Medical devices may include all natural and synthetic materials, as well as both fibrous and non-fibrous materials. For example, materials may be composed of metals, plastics, paper, glass, ceramics, fabrics, rubber, polymers, composites, or any other material or combination of materials. Exemplary medical devices include, but are not limited to, catheters of any type; cannulas; needles; stents of any size, shape, or configuration; coils of any size, shape, or configuration; contact lenses; IUDs; peristaltic pump chambers; endotracheal tubes; gastrointestinal feeding tubes; arteriovenous shunts; condoms; artificial lungs and kidney membranes; gloves; pacemaker leads; wound dressings; metal pins, plates, and screws; metal hip prostheses; knee prostheses; gels; creams and ointments.

[0046] Bioprostheses include, but are not limited to, prostheses made of biological materials. Examples include heart valves, pericardium, vascular grafts, bladder prostheses, tendon prostheses, hernia patches, surgical meshes and skin substitutes. In one embodiment, the nanoreservoirs of the present invention can be used to coat a bioprosthetic heart valve, such as a decellularized porcine heart valve or bovine pericardium. In another aspect, the present invention provides a bioprosthetic heart valve, such as a decellularized porcine heart valve or bovine pericardium coated with the nanoreservoirs of the present invention.

[0047] In one embodiment of the present invention, the nanoreservoirs of the present invention can be fixed or attached to the surface of a medical device, biomaterial implant or bioprosthesis using various physical or chemical strategies such as electrografting (electrical initiation of polymerization by polarizing a metal surface in the presence of a monomer), surface irradiation, layer-by-layer (LbL) assembly, spin-coating, chemical vapor deposition (CVD), laser deposition, blood proteins, mussel-inspired coatings, plant phenols (Qiang Wei and Rainer Haag, 2005, Mater. Horiz. 2015, 2:567-577, Universal polymer coatings and their representative biomedical applications).

[0048] According to another aspect of the invention, there is provided a nanoreservoir formed by crosslinking a first polymer with a second polymer, the first polymer having one or more catechol moieties and the second polymer comprising a hydrophilic backbone having one or more reactive moieties, the polymers may be crosslinked in the presence of one or more bioactive agents to produce a nanoparticle comprising the first and second polymers with the bioactive agents entrapped therein.

[0049] In yet a further embodiment, a method of forming a nanoreservoir is provided that includes crosslinking a first polymer having one or more catechol moieties with a second polymer that includes a hydrophilic backbone having one or more reactive moieties. The nanoreservoir produced preferably comprises nanoparticles of the crosslinked polymer.

[0050] In a preferred embodiment, the method of making a nanoreservoir comprises: i) obtaining P(mDOPA); [ka] ii) oxidizing P(mDOPA) to form an aqueous solution of Pox(mDOPA); [ka] iii) adding the PAH solution to the aqueous solution of Pox(mDOPA); [ka] iv) cross-linking the compounds of ii) and iii) to form a nanogel solution of nanoparticles of the formula: [ka] Includes.

[0051] In a preferred embodiment, the present invention provides a method for making nanoreservoirs containing at least two bioactive molecules, therapeutic molecules or drugs, the method comprising: i) mixing Pox(mDOPA) in an aqueous solution with one biologically active molecule, therapeutic molecule or drug; ii) adding a PAH solution to the resulting aqueous solution of Pox(mDOPA) obtained in i) to form a first nanogel solution; iii) repeating steps i) and ii) with a second bioactive molecule, therapeutic molecule or drug to form a second nanogel solution; iv) mixing the first and second nanogel solutions to obtain nanoreservoirs carrying two bioactive molecules, therapeutic molecules or drugs; Includes.

[0052] The nanoreservoirs may be comprised of a ratio of nanogel loaded with a first bioactive molecule, therapeutic molecule or drug to nanogel loaded with a second bioactive molecule, therapeutic molecule or drug of between about 1 part first bioactive molecule, therapeutic molecule or drug and about 5 parts second bioactive molecule, therapeutic molecule or drug, or about 2 parts first bioactive molecule, therapeutic molecule or drug and about 3 parts second bioactive molecule, therapeutic molecule or drug.

[0053] The first bioactive molecule, therapeutic molecule or drug can be an antibiotic. The second bioactive molecule, therapeutic molecule or drug can be an antiplatelet agent.

[0054] According to another aspect, the present invention provides a method for producing a medical device, biomaterial implant or bioprosthesis having a coated surface comprising coating the surface of the medical device, biomaterial implant or bioprosthesis with nanoreservoirs according to the present invention.

[0055] The method is: i) immersing the surface to be coated in a solution of a first polymer; ii) oxidizing the first polymer; iii) immersing the resulting surface in a second polymer solution; iv) immersing the surface in a solution of the nanoreservoirs described herein to form a coating on the surface; v) optionally immersing the coated surface in a solution of a hydrophilic functionalizing ligand; may include.

[0056] The first polymer can be P(mDOPA). The oxidized form of the first polymer can be Pox(mDOPA). The second polymer can be PAH.

[0057] The nanoreservoirs in step iv) may comprise nanoparticles of a nanogel formed by crosslinking a first polymer with a second polymer, the first polymer may be P(mDOPA) and the second polymer may be a PAH.

[0058] The nanoreservoirs in step iv) may contain one or more, preferably two or more, bioactive molecules, therapeutic molecules and / or drugs. Bioactive molecules may include antibiotics and / or antiplatelet agents.

[0059] A medical device, biomaterial implant or bioprosthesis coated with nanoreservoirs containing two or more layers of nanoparticles can be produced by repeating steps iii) and iv) of the above method. Nanoreservoirs containing 2, 3, 4, 5 or more layers can be produced.

[0060] The bioprosthesis may be a prosthetic heart valve.

[0061] The method of the invention may be used to coat only a portion of the surface of a medical device, biomaterial implant or bioprosthesis, or substantially the entire or entire surface of a medical device, biomaterial implant or bioprosthesis.

[0062] The invention further provides a coated medical device, biomaterial implant or bioprosthesis according to the invention or produced by a method of the invention for use in preventing or reducing infection when the medical device, biomaterial implant or bioprosthesis is implanted in a subject.

[0063] The present invention further provides a nanoreservoir according to the present invention or produced by a method of the present invention for use in preventing or reducing infection upon implantation of a medical device, biomaterial implant or bioprosthesis in a subject. The subject may be a mammal, preferably a human.

[0064] According to another aspect of the present invention there is provided a method of coating a surface of a medical device, biomaterial implant or bioprosthesis with nanoreservoirs, the method comprising: i) immersing the surface to be coated in a solution of P(mDOPA); ii) oxidizing P(mDOPA) to form Pox(mDOPA); iii) immersing the resulting surface in a PAH solution; iv) immersing the surface in a solution of nanoreservoirs according to the invention; v) optionally immersing the resulting coated surface in a solution of a hydrophilic functionalizing ligand; Includes.

[0065] According to another aspect of the invention, there is provided a method of coating a surface of a medical device, biomaterial implant or bioprosthesis with nanoreservoirs containing two or more different bioactive molecules, therapeutic molecules or drugs, the method comprising: i) immersing the surface in a solution of p(mDOPA); ii) oxidizing p(mDOPA) to form Pox(mDOPA); iii) immersing the resulting surface in a PAH solution; iv) immersing the surface in a solution of nanoreservoirs according to the invention containing two or more bioactive molecules, therapeutic molecules or drugs; v) repeating steps iii) and iv) at least 3, 4 or 5 times to build up a multi-layer coating; and optionally vi) immersing the coated surface in a solution of a hydrophilic functionalizing ligand; Includes.

[0066] According to a further aspect, there is provided a biomaterial implant, medical device or bioprosthesis, such as an artificial heart valve, at least partially coated with nanoreservoirs comprising at least 2, 3, 4, 5, 6 or more layers according to the invention. Preferably, at least one layer of the nanoreservoirs comprises at least two bioactive molecules, therapeutic molecules or drugs. Preferably, the outermost layer of the nanoreservoir carries functional groups according to the invention.

[0067] According to a further aspect of the invention, there is provided a nanoreservoir formed by crosslinking a first polymer with a second polymer, wherein the first polymer has one or more catechol moieties and the second polymer comprises a hydrophilic backbone having one or more reactive moieties, and optionally the nanoreservoir contains one or more bioactive molecules, therapeutic molecules or drugs, for use as a coating on a biomaterial implant, medical device or bioprosthesis.

[0068] According to another aspect of the present invention, a compound according to at least formula I: [ka] The nanoreservoir includes a nanogel comprising a polymer of the formula: wherein the hydrophilic polymer backbone comprises one or more of polyallylamine, polyvinylamine, polyvinylamide, polyvinyl alcohol, poly(meth)acrylate, poly(meth)acrylamide, polyurethane or PEG or polyelectrolytes (cationic, anionic or zwitterionic) or hydrophilic biopolymers (e.g. polysaccharides such as chitosan or hyaluronan).

[0069] According to a further aspect of the invention, a compound of formula I: [ka] In one embodiment, the nanoreservoir comprises a nanogel formed by crosslinking a polymer of the formula (I) , wherein the hydrophilic polymer backbone comprises one or more of polyallylamine, polyvinylamine, polyvinylamide, polyvinyl alcohol, poly(meth)acrylate, poly(meth)acrylamide, polyurethane or PEG or polyelectrolytes (cationic, anionic or zwitterionic) or hydrophilic biopolymers (e.g. polysaccharides such as chitosan or hyaluronan).

[0070] In a further aspect of the invention, the nanoreservoirs according to the invention can be used in coating compositions on medical devices, biomaterial implants or bioprostheses.

[0071] In a further aspect of the invention there is provided the use of a nanoreservoir according to the invention as a coating on a medical device, biomaterial implant or bioprosthesis.

[0072] In a further aspect of the invention there is provided the use of a nanoreservoir according to the invention as a coating composition on a medical device, a biomaterial implant or a bioprosthesis.

[0073] In another embodiment of the invention, the nanoreservoirs can be used in coating compositions on medical devices, biomaterial implants or bioprostheses, where the nanoreservoirs contain one or more bioactive compounds or drugs.

[0074] In a further aspect, the present invention provides a medical device, biomaterial implant or bioprosthesis having a nanoreservoir of the present invention on a surface thereof. The surface of the medical device, biomaterial implant or bioprosthesis may be coated with the nanoreservoir of the present invention.

[0075] A biomaterial implant, medical device or bioprosthesis, or a portion thereof, can be coated with the nanoreservoirs of the present invention by immersing the biomaterial implant, medical device or bioprosthesis in a solution containing the nanoreservoirs of the present invention or by spraying the biomaterial implant, medical device or bioprosthesis with a solution containing the nanoreservoirs of the present invention, and then allowing the coated biomaterial implant, medical device or bioprosthesis to dry.

[0076] In the present invention, the nanoreservoirs can be configured to be anti-adhesive to both platelets and bacteria, and can be configured to store and / or deliver therapeutic and / or active molecules, such as biological and non-biologically active molecules (e.g., drugs, biologics), with or without an associated coating that controls the delivery rate of the therapeutic or active molecules to the surrounding tissue. The delivery rate may span a release period of at least 1 day, 2 days, 3 days, 7 days, while the anti-adhesive efficacy will be maintained for at least 1 month, at least 2 months, at least 3 months, at least 4 months, at least 5 months, or at least 6 months.

[0077] In a preferred embodiment, the nanoreservoir contains an antibiotic and an antiplatelet agent. In a further preferred embodiment, the nanoreservoir contains minocycline and ticagrelor. In a preferred embodiment, the nanoreservoir contains an antibiofilm agent and an anticoagulant. In a preferred embodiment, the nanoreservoir contains an antibiofilm agent and an antiplatelet agent.

[0078] According to another aspect of the present invention, (i) mixing a quinone-functionalized polymer in an aqueous solution in the presence of one or more bioactive molecules or drugs; (ii) adding a polymer solution to the aqueous solution to form a nanogel solution, the polymer being selected from one or more of polyallylamine, polyvinylamine, polyvinylamide, polyvinyl alcohol, poly(meth)acrylate, poly(meth)acrylamide, polyurethane or PEG or polyelectrolytes (cationic, anionic or zwitterionic) or hydrophilic biopolymers (e.g. polysaccharides such as chitosan or hyaluronan); A method of making a nanoreservoir is provided, comprising:

[0079] According to another aspect of the present invention, (i) mixing the quinone-functionalized polymer Pox(mDOPA) in an aqueous solution with one or more biologically active molecules, therapeutic molecules or drugs; (ii) adding the PAH solution to an aqueous solution of Pox(mDOPA) to form a nanogel solution; A method of making a nanoreservoir is provided, comprising:

[0080] In a preferred embodiment of the invention, there is an initial step of oxidizing p(mDOPA) to form Pox(mDOPA).

[0081] In a further embodiment of the invention, there is an additional step of freeze-drying the nanogel solution.

[0082] In a preferred embodiment of the invention, the aqueous solution of Pox(mDOPA) and / or PAH has a pH of at least 8, preferably at least 10.

[0083] The present invention also provides (i) dissolving a first polymer, such as methacrylamide with 3,4-dihydroxy-L-phenylalanine (P(mDOPA)), in distilled water to produce oxidized P(mDOPA); (ii) adding NaOH (0.1 M) to an aqueous solution of oxidized P(mDOPA) at room temperature; (ii) adding the PAH solution at about pH 10 to the aqueous solution of oxidized P(mDOPA) with vigorous stirring at room temperature for at least 1 hour; The present invention provides a method for making a nanogel comprising:

[0084] Preferably in step (ii), NaOH and oxidized P(mDOPA) are mixed for at least 6 hours, preferably overnight. Preferably, the pH of the solution is 10 or greater.

[0085] According to a further aspect of the present invention, (i) dissolving methacrylamide with 3,4-dihydroxy-L-phenylalanine (P(mDOPA)) in distilled water in the presence of a biologically active molecule or drug at 6° C. for 1 hour to generate oxidized P(mDOPA); (ii) adding NaOH (0.1 M) to an aqueous solution of oxidized P(mDOPA) at room temperature overnight; (ii) adding the pH 10 PAH solution to the aqueous solution of oxidized P(mDOPA) with vigorous stirring at 6° C. overnight; A method for making a nanogel is provided, comprising:

[0086] According to another aspect of the invention there is provided a nanogel obtained by any of the methods of the invention.

[0087] It will be understood that optional features applicable to one aspect or embodiment of the invention can be used in any combination and in any number. Moreover, they can also be used in any combination and in any number with any of the other aspects or embodiments of the invention. This includes, but is not limited to, dependent claims from any claim used as a dependent claim of any other claim in this application.

[0088] The invention will now be further described, by way of non-limiting examples only, with reference to the following figures and experimental examples. [Brief description of the drawings]

[0089] [Figure 1] FIG. 1 shows the chemical structures of (1) P(mDOPA), (2) Pox(mDOPA), and (3) PAH. [Diagram 2] FIG. 1 shows a strategy for forming Pox(mDOPA) / PAH nanogels. [Diagram 3] FIG. 1 shows TEM analysis of nanogels according to the invention (a) without lyophilization and (b) with lyophilization. [Figure 4] FIG. 1 shows DLS analysis of nanogel solutions. [Diagram 5] FIG. 1 shows DLS analysis of nanogel, nanogel(ABT) and nanogel(ABT-Tica). [Figure 6] FIG. 2 shows the modification of a Ti surface with a polydopamine (PDOPA) layer, where PAH and nanogels are self-crosslinked via Schiff base bonds on the PDOPA-coated Ti substrate. [Figure 7] FIG. 1 shows images of Ti surfaces before and after PDOPA modification. [Figure 8] FIG. 1 shows field emission scanning electron microscope (SEM) observations. [Figure 9] FIG. 13 shows the deposition of nanoreservoirs analyzed by quartz crystal microbalance. [Figure 10] FIG. 2 illustrates modification of a Ti surface with a nanogel according to the present invention. [Figure 11]FIG. 1 shows an SEM analysis of a nanogel according to the invention deposited on a Ti surface according to a second technique. [Figure 12] FIG. 1 shows photographs of biological valves before and after PDOPA modification. [Figure 13] SEM images of the biological valve surface before nanogel deposition (top left) and after nanogel deposition with (top right) or without (bottom left) PDOPA coating (magnification = 5000x). [Figure 14] SEM images of the biological valve surface before nanogel deposition (top left) and after nanogel deposition with (top right) or without (bottom left) PDOPA coating (magnification = 30000x). [Figure 15] Dynamic hemocompatibility testing using the Impact-R system at a constant shear rate of 1800 s-1 for 2 min. The effect of shear stress on platelet adhesion (left graph) and aggregate formation (right graph) at different time points using two types of polymer-coated PEG or APEG is shown. Median values ​​for healthy donors (N=4) are reported in both graphs. Statistical analysis was performed using Graph Pad software with grouped two-way ANOVA and Bonferroni post-hoc test. Furthermore, platelet adhesion correlated with the water contact angle of the coating on the glass support, with surfaces with smaller contact angles (i.e., more hydrophilic PEG surfaces) resulting in less platelet adhesion. [Figure 16] Dynamic impact R-studies at a constant shear rate of 1800 s-1 for 2 min (A and B) or 4 min (C). A: Median SC and AS measured for 3 healthy donors (duplicates per donor per condition). B: Representative photograph of the study shown in A. [Figure 17] Figure 1 shows dynamic impact R test at constant shear rate of 1800 sec-1 for 4 minutes. Platelet count was measured after shear stress application. Tests were performed in quadruplicate on one donor. [Figure 18]Static test to analyze blood cells attached to nanogel modified surfaces. Blood was incubated on 24-well polystyrene non-coated (NC) or coated with Nanogel (NG) or Nanogel Peg (NP) or Nanogel Antibiotics Peg (NAP). Cells attached to the surface were stained with crystal violet. Images of cells fixed on polystyrene surfaces were processed. Images were taken with a light microscope Olympus CKX41 (magnification 20x). The number of cells was counted in each field using Fiji Software (particle analysis plugin). Numbers represent the average of 8 fields per condition. [Figure 19] Platelet-rich plasma (PRP) at a concentration of 250,000 platelets / μl was incubated under static conditions for 1 min (A) or 45 min (B) on wells coated with PS NC (non-coated polystyrene) or NAP (nanogel antibiotic PEG) at 37° C. After washing three times with 0.9% NaCl, platelets were stained with May-Grünwald solution and observed under an Olympus CKX41 light microscope (10x magnification). [Figure 20] Figure 14 Quantification of S. aureus biofilms using crystal violet. Bacteria were grown for 24 h on polystyrene surfaces modified with antibiotic-loaded or non-loaded nanogels as indicated. [Figure 21] FIG. 1 shows SEM analysis of biological valve surfaces after 24 h incubation with Staphylococcus aureus, comparing uncoated and nanogel modified surfaces (magnification=2000x). [Figure 22] Figure 1 shows C. faecalis bacteria grown for 24 hours on modified polystyrene surfaces under static or shaking conditions, with CFU counts of planktonic bacteria plated on TSB agar plates. [Diagram 23]Figure 1 shows the results of a study of the antithrombotic properties of nanoreservoirs in solution by platelet aggregation assay. (A) PRP was preincubated for 10 min with a solution of nanoreservoirs without ticagrelor or containing increasing concentrations of ticagrelor as indicated. Platelet aggregation was induced by adding 10 μM ADP at 37 ° C under stirring conditions (1200 rpm). The percentage of maximum aggregation recorded by light transmission aggregometry is shown. Data represent the mean ± SD (*p < 0.05, **p < 0.01, ***p < 0.001). (B) Maximum platelet aggregation obtained in the presence of different ratios of ticagrelor-loaded nanogels and minocycline-loaded nanogels. NG indicates nanogels with PEG1500, NGT indicates ticagrelor-loaded nanogels with PEG1500, NGM indicates minocycline-loaded nanogels with PEG1500. Data represent the mean ± SD. [Figure 24] Figure 1 shows the results of a study of the effect of immobilized nanoreservoirs on the activation of the coagulation contact phase in human plasma. Standard plasma was incubated for 10 min on coated and uncoated PS surfaces. Minocycline-loaded and ticagrelor-loaded nanogels mixed in a ratio of 2 / 3 (NGT60:NGM40) are compared with a nanogel loaded with two drugs (NGTM). Basal indicates plasma not in contact with the test surface. NC indicates uncoated. Data represent the mean ± SD. [Diagram 25] Results of a study of multilayer nanogel assemblies on S. aureus biofilm formation. (A) Bacteria were allowed to adhere to coated and uncoated PS surfaces for 24 h, followed by crystal violet staining. Data represent the mean ± SD. (B) Bacteria were allowed to adhere to coated and uncoated titanium surfaces for 24 h, followed by crystal violet staining. Data are representative of two independent experiments. NC is uncoated, NG is unloaded nanogels with PEG1500, LBL is 1,3,5,5:1,3 and 5 layer nanogel mixtures loaded with minocycline and ticagrelor in a 2 / 3 ratio. [Figure 26]Figure 1 shows the results of the study of multilayered nanogel assemblies on the antiplatelet effect of nanoreservoirs. NC is uncoated, NG is unloaded nanogels with PEG1500, LBL is 1,3,5,5:1,3 and 5 layer nanogel mixtures loaded with minocycline and ticagrelor in a 2 / 3 ratio. Data represent the mean ± SD. [Figure 27] Figure 1 shows that cross-linking of 5-layer nanogels with dopamine sustains antibiotic efficacy against S. aureus biofilm formation for more than 48 hours. (A) Surfaces were incubated twice for 24 hours with fresh medium, followed by the addition of S. aureus bacteria. Biofilm formation was quantified by crystal violet staining after 24 hours. (B) Anti-biofilm effect of medium removed after a second 24 hour contact with the test surface. NC is uncoated, NG is 5-layer nanogels with PEG1500, NTMV is 5-layer nanogels with PEG1500 loaded with ticagrelor, minocycline and vancomycin, D-NTMV is dopamine cross-linked 5-layer nanogels with PEG1500 loaded with ticagrelor, minocycline and vancomycin. Data represent mean ± SD. [Figure 28] Figure 1 shows the results of in vivo analysis of the anti-biofilm efficacy of nanoreservoirs immobilized on titanium implants. (A) S. aureus pre-infected titanium disks were implanted subcutaneously in mice (n=3) and after 3 h, live bacteria on the implants were analyzed by CFU counting. (B) Surface analysis of the implants by SEM (magnification 2000x) is shown. [Figure 29] FIG. 1 shows the 1H NMR spectrum of thiol end-functionalized PEG1.5 recorded in CDCl3 with peak assignments. [Diagram 30] (A) H NMR spectrum of the polymerization (2-(methacryloyloxy)ethyl phosphorylcholine) recorded at D20 with peak assignments. (B) Aqueous size-exclusion chromatograms of four different molecular weights of these polybetaines. [Diagram 31]Figure 1 shows an LDH activity assay of platelet adhesion to polystyrene surfaces. PRP was incubated for 45 min on the indicated coated and uncoated surfaces. NC is uncoated, NG is 5-layer nanogel with PEG1500, NTM is minocycline and ticagrelor-containing nanoreservoirs (5-layer nanogel-PEG1500 ratio 2 / 3), NTM-APEG1 is minocycline and ticagrelor-containing nanoreservoirs (5-layer nanogel-PEG acrylate 1000 ratio 2 / 3), NTM-APEG2 is minocycline and ticagrelor-containing nanoreservoirs (5-layer nanogel-PEG acrylate 2000 ratio 2 / 3). Data represent the mean ± SD. [Diagram 32] Figure 1. S. aureus biofilm formation on coated and uncoated titanium implants with 5-layer nanogels bearing different ligands with thiol or vinyl functionalized ends. Bacteria were allowed to attach for 3 h before CFU counting. NC is uncoated, NG-PB15 is 5-layer nanogels with polybetaine 15 kD as the final layer, NG-P1.5, NG-P2 are 5-layer nanogels with PEG 1.5 kD or 2 kD as the final layer. NG-APEG0.5 is 5-layer nanogel-PEG acrylate 500, NG-APEG1 is 5-layer nanogel-PEG acrylate 1000. Data represent mean ± SD. [Diagram 33] Figure 1. S. aureus biofilm formation on coated and uncoated PS surfaces with 5-layer nanogels with different molecular weights of PEG. Bacteria were allowed to attach for 24 h before biofilm quantification by crystal violet staining. Control is uncoated, NG is 5-layer nanogel without grafted polymer, NG-P1.5, NG-P2, NG-P5, NG-P10 are 5-layer nanogels with PEG 1.5kD, 2kD, 5kD, 10kD as the final layer. Data represent mean ± SD. [Diagram 34]Results of a study of the effect of thiol-terminated PEG of different molecular weights on platelet adhesion under flow using Impact-R. Citrated whole blood was added to the PS wells, followed by 780 rpm for 4 min. Surface coverage (SC) and aggregate size (AS) were determined. NC denotes uncoated, NG denotes 5-layer nanogels without grafted polymer, NG-P1.5, NG-P2, NG-P5, NG-P10 denote 5-layer nanogels with PEG 1.5 kD, 2 kD, 5 kD, 10 kD as the final layer. Data represent mean ± SD. [Diagram 35] Figure 1 shows the results of a study of the effect of 5-layer nanogels with PEG thiols of different molecular weights on the activation of the contact phase of coagulation. After 10 min incubation of standard human plasma at 37 °C, the clotting time was analyzed in the presence of Nodia non-activated partial thromboplastin time (NaPTT) reagent. Kaolin is used as a positive control. CTI denotes corn trypsin inhibitor, NC denotes uncoated, NG denotes 5-layer nanogels without grafted polymer, NG-P1.5, NG-P2, NG-P5, NG-P10 denote 5-layer nanogels with PEG 1.5 kD, 2 kD, 5 kD, 10 kD as the final layer. Data represent the mean ± SD. [Diagram 36] Figure 1. S. aureus Xen-29 biofilm formation on PS surfaces coated with 5-layer nanogels with or without PEG thiol or different molecular weight polybetaines. After 4 h of bacterial attachment, the medium was removed and photon emission was quantified, either immediately (upper panel) or after 2 h (lower panel), and is directly proportional to bacterial attachment. NC is uncoated, NG is 5-layer nanogels without grafted polymer, NG-PB7, NG-PB15, NG-PB44, NG-PB70 are 5-layer nanogels with polybetaine 7 kD, 15 kD, 44 kD, 70 kD as the final layer, and NG-P2 is 5-layer nanogel with PEG 2 kD as the final layer. Data represent mean ± SD. [Figure 37]Figure 1 shows the results of a study of the effect of thiol-terminated PEG and polybetaine on platelet adhesion under flow using Impact-R. Citrated whole blood was added to the PS wells, followed by 780 rpm for 4 min. Surface coverage (SC) and aggregate size (AS) were determined. NC is uncoated, NG is a 5-layer nanogel without grafted polymer, NG-PB7, NG-PB15, NG-PB44, NG-PB70 are 5-layer nanogels with polybetaine 7 kD, 15 kD, 44 kD, 70 kD as the final layer, and NG-P2 is a 5-layer nanogel with PEG 2 kD as the final layer. Data represent the mean ± SD. [Figure 38] Figure 1 shows the results of a pNPP assay of platelet adhesion to polystyrene surfaces. PRP was incubated for 45 min on the indicated coated and uncoated surfaces. NC is uncoated; NG-PB7, NG-PB15 are 5-layer nanogels with polybetaine 7 or 15 kD as the final layer; NG-P1.5, NG-P5 are 5-layer nanogels with PEG 1.5 kD or 5 kD as the final layer; NG-APEG0.5 is 5-layer nanogel-PEG acrylate 500; NG-APEG1 is 5-layer nanogel-PEG acrylate 1000. Data represent the mean ± SD. [Figure 39] Figure 1 shows the results of a study of the effect of 5-layer nanogels with PEG thiol or polybetaine of different molecular weights on the activation of the contact phase of coagulation. After incubation of standard human plasma for 10 min at 37 °C, the clotting time was analyzed in the presence of Nodia non-activated partial thromboplastin time (NaPTT) reagent. Kaolin is used as a positive control. NC is uncoated, NG is 5-layer nanogel without grafted polymer, NG-PB7, NG-PB15, NG-PB44 are 5-layer nanogels with polybetaine 7 kD, 15 kD, 44 kD as the final layer, NG-P1.5, NG-P2, NG-P5 are 5-layer nanogels with PEG 1.5 kD, 2 kD, 5 kD as the final layer. Data represent the mean ± SD. [Diagram 40]Figure 1 Quantification of plasma proteins attached to coated and uncoated polystyrene surfaces after incubation of standard human plasma for 10 min at 37 °C. NC is uncoated, NG is 5-layer nanogels without grafted polymer, NG-PB7, NG-PB15, NG-PB44 are 5-layer nanogels with polybetaine 7 kD, 15 kD, 44 kD as the final layer, NG-P1.5, NG-P2, NG-P5 are 5-layer nanogels with PEG 1.5 kD, 2 kD, 5 kD as the final layer. Data represent mean ± SD.

[0090] Having generally described the invention, it will be more readily understood by reference to the following examples, which are included solely for purposes of illustrating certain aspects and embodiments of the invention and are not intended to limit the invention in any way.

[0091] material and method material reagent Antibiotics (minocycline, vancomycin) were purchased from Sigma, and the antiplatelet drug ticagrelor was purchased from Cayman Chemicals.

[0092] Blood Collection Tube : Sodium Citrate Vacutainer tubes (3.2% sodium citrate) were obtained from BD Biosciences.

[0093] Bacterial strains and media Staphylococcus epidermidis, strain RP62A (#35984) was obtained from ATCC, S. aureus, E. faecalis were purchased from ATCC (25904 and 29212), and S. aureus Xen29 bioluminescent pathogenic bacteria was obtained from Perkin Elmer (#119240). Tryptic soy broth (TSB) and agar powder were obtained from Sigma-Aldrich.

[0094] Sample preparation Sterilization of surfaces prior to in vitro testing: All surfaces, coated or uncoated, were sterilized in 100% absolute ethanol for 10 min, followed by incubation in distilled water for 2–5 min and one wash with 0.9% NaCl.

[0095] Blood from healthy donors (medicated and had not taken aspirin or other anticoagulants in the last 20 days before blood collection) was drawn either directly into 50 mL polypropylene tubes containing 3.2% sodium citrate (1 volume of citrate for 9 volumes of blood) using an 18 g needle for static tests or using a 21 g needle and citrate vacutainer tubes for dynamic tests. The study was approved by the Ethics Committee of the University Hospital of Liège, Belgium. Donors signed informed consent.

[0096] Experiments using Staphylococcus aureus were carried out in a biosafety level 2 room at GIGA-R.

[0097] Dynamic in vitro Impact-R testing The blood was allowed to sit in the tube for 45 min before any treatment with a cone-plate device, Impact-R system (Matis Medical). The blood was then mixed at room temperature for 1 min at 10 rpm before shear stress was applied. For each test, 130 μL of blood was carefully placed into the well. The applied shear stress was 1800 s-1 for 4 min (corresponding to a bell speed of 780 rpm). This speed and incubation time simulate laminar arterial blood flow over a polystyrene surface and are useful for analyzing platelet function under shear stress.

[0098] After 4 min of shear stress, blood was collected and a single platelet count was analyzed by Cell Dyn, during which coated or uncoated PS wells were gently washed 4 times with distilled water and stained with May-Grünwald staining solution for 1 min at room temperature. Platelets attached to the surface were visualized by light microscopy and quantified using Impact-R software. Two parameters were obtained from the analysis: (i) surface coverage (SC%) and (ii) platelet aggregate size (AS μm). Each condition was repeated in duplicate for each donor.

[0099] Static in vitro testing Platelet adhesion on the surface was analyzed using one of the photometric assays LDH (lactate dehydrogenase test) and p-nitrophenyl phosphate (pNPP) test. The values ​​obtained from both tests are directly proportional to the number of platelets attached to the surface. LDH released during platelet lysis is analyzed indirectly by measuring the conversion of NAD to NADH, detected at 450 nm. The pNPP test measures the levels of alkaline and acid phosphatases released during platelet lysis. Hydrolysis of pNPP, a substrate for these phosphatases, produces p-nitrophenol, which has a maximum absorbance at 405 nm and is proportional to the amount of platelets bound to the surface.

[0100] Platelet-poor plasma (PPP) or platelet-rich plasma (PRP) was layered onto the coated polystyrene surface for 45 min at 37°C. The surface was washed three times with 0.9% NaCl. Lysis of attached platelets was achieved by adding 1% Triton in PBS for the LDH test and 5 mM pNPP in 1% Triton in sodium citrate buffer (0.05 M citric acid pH 5.4) for the pNPP assay. Background readings from the PPP incubation were subtracted from the PRP readings.

[0101] Platelet aggregation test Platelet-rich plasma (PRP) was prepared by centrifugation of citrate-anticoagulated human blood at 100 × g for 15 min at room temperature. Platelet aggregation experiments were performed on PRP aliquots using optical aggregometry (Chrono-Log Model 700 aggregometer, Kordia) with stirring (1200 rpm) at 37 °C.

[0102] Plasma-biomaterial interactions: clotting assays and plasma protein adhesion Coagulation studies were performed using a Stago STart® 4 Hemostasis Analyzer and Nodia non-activated partial thromboplastin time (NaPTT) reagent. The NaPTT reagent is a synthetic phospholipid platelet substitute intended for the study of activation of the clotting contact phase. The Stago Analyzer is a semi-automated system integrated with an electromechanical clot detection method (a viscosity-based detection system). Clot formation in citrated human standard plasma (Stago) was mediated by Ca as well as phospholipids. 2+ The clotting time is catalyzed by the addition of ions. Kaolin was used as a positive control for contact phase activation, while corn trypsin inhibitor (CTI), a specific inhibitor of factor XIIa, the factor that initiates the contact activation pathway, was used to determine the clotting time independently of this pathway. Standard human plasma was thawed in a 37°C water bath and added to coated and uncoated polystyrene (PS) wells for 10 min at 37°C without stirring. The plasma was then flash frozen in a dry ice / acetone bath (-78°C) and stored at -80°C until analysis. On the day of the test, the plasma was thawed at 37°C and immediately processed in four Stago STart® instruments. Pre-warmed 37°C Nodia reagent was added to 100 μl of pre-warmed plasma in a cuvette containing coated metal beads, after which clotting was initiated by the addition of pre-warmed calcium solution (8.3 mM). The clotting end point is measured by the pendulum motion of the beads aligned by an electromagnetic field. Such movement is influenced by the viscosity of the plasma and ceases when viscosity is at a maximum, i.e., when plasma coagulation occurs.

[0103] Protein attachment was measured using the Pierce Micro BCA (bicinchonic acid) assay, a highly sensitive method that detects up to 5ng / ml of protein. + It binds Cu ions with a 2:1 stoichiometry, providing high sensitivity. The assay is based on the detection of Cu by proteins in a basic environment. 2+ Cu ions + The conversion is based on the 120 μl plasma (Stago Standard Plasma) pre-warmed to 37°C was added to coated and uncoated wells of a 48-well polystyrene (PS) plate (11 mm diameter wells) and incubated for 10 min at 37°C. After three washes with 0.9% NaCl, the attached proteins were detached by adding 250 μl of a solution of 1% SDS in PBS for 10 min at room temperature. The undiluted protein solution was used in the Micro BCA assay.

[0104] Bacterial adhesion and biofilm formation analysis A single colony of S. epidermidis, S. aureus, or E. faecalis was grown overnight at 37°C in TSB medium with agitation (220 rpm), and a 1:100 dilution was made the next day in fresh TSB medium and the suspension was incubated until it reached log phase (OD 595= 0.5) for 4 h. Bacteria were then diluted 1 / 20 in sterile NaCl 0.9% to approximately 200,000 cfu / μl and 500 μL was incubated in coated or uncoated polystyrene 24-well plates at 37 °C for 24 h under static or dynamic conditions. Bacterial suspensions were analyzed by agar plating and CFU (colony forming unit) counting, and biofilms were analyzed by crystal violet staining. Surfaces were first washed three times with NaCl 0.85% to remove planktonic bacteria and then stained with 1% crystal violet for 40 min. After three washes with water, the crystal violet dye retained in the bacteria was released with 10% acetic acid for 10 min. Intensity was measured at 595 nm in 96-well plates using a spectrophotometer plate reader. Conditions were in duplicate and readings were in triplicate. The kinetics of bacterial attachment and biofilm formation on surfaces was also evaluated by using bioluminescent Staphylococcus aureus bacteria with the IVIS Lumina system (Perkin Elmer). After allowing bacteria to attach for 3 hours, the wells were washed and then the luminescence signal, which is directly proportional to the bacterial density, was recorded over time. Biofilms were imaged using an IVIS camera system. Total photon emission from selected wells was quantified using the LivingImage software package.

[0105] A murine model of biomaterial-associated infection: Subcutaneous implantation of titanium devices prior to infection and in vivo biofilm formation S. aureus was grown for 2 h at 37°C in TSB medium until it reached logarithmic phase. Bacteria were diluted 1:10,000 in TSB supplemented with 2% NaCl + 1% glucose and 800 μl aliquots (corresponding to 20,000 CFU / disc) were layered onto 0.2 cm diameter titanium discs (Biotronik). Bacteria were allowed to attach to all discs for 3 h at 37°C under static conditions. The bacterial suspension was removed and the surfaces were gently washed three times with PBS. To determine the number of bacteria attached onto the titanium discs, half of the discs were sonicated for 5 min in a Fisher water bath sonicator. The isolated bacteria were plated on TSB agar plates to determine the number of colony forming units (CFU) per disc before implantation. The other half of the discs was implanted into 8-week-old male BALB / cJRj mice (Janvier Laboratories) as follows: Two hours prior to anesthesia, mice were subcutaneously injected with 0.05 mg / kg buprenorphine analgesic (Temgesic). Fifteen minutes prior to implantation, mice were anesthetized by intraperitoneal injection of a ketamine (125 mg / kg) / xylazine (12.5 mg / kg) mixture. The lower ventral side of the lower rib cage of mice was shaved and the area was sterilized with betadine followed by a 70% ethanol solution. A sterile scalpel was used to incise the skin and S. aureus infected or non-infected disks were inserted between the skin and muscle. After 4 hours of incubation, mice were sacrificed by cervical dislocation and the devices were analyzed to determine CFU / disc (by sonication as previously described). The protocol was approved by the ethical committee of ULiege University (#16-1774). SEM images of the explanted titanium disks were taken with a Quanta Microscope (magnification 4000x). Titanium discs were gently washed and fixed in 2.5 glutaraldehyde in Sorensen's buffer for 1 h at 4 °C, followed by three washes in Sorensen's buffer and 2% OsO 4 The discs were then fixed in ethanol for 1 h at 4 °C. The discs were then dehydrated in increasing concentrations of ethanol and incubated in CO to preserve the biological structure. 2 It was dried under atmosphere (critical point drying) and then metallized.

[0106] Results and Discussion example Example 1: Preparation of crosslinked nanogels and loading of bioactive molecules A homopolymer of methacrylamide with 3,4-dihydroxy-L-phenylalanine (P(mDOPA), 1, Figure 1) was specifically designed to prepare nanogels and to immobilize active (bio)molecules by physical entrapment or covalent attachment. The crosslinked reactive nanogels can be directly deposited onto surfaces pre-coated with a bioinspired polydopamine layer. This strategy has several advantages over existing methods, including: i) no external crosslinking agents are used, ii) the coupling reaction is fast at room temperature and in water, iii) no undesired by-products are formed and released from the film, and iv) active biomolecules can be covalently attached to the surface.

[0107] A fast, water-based cross-linking process was used to exploit the redox properties of the DOPA molecule to provide reactive functionality available for nanogel formation and nanogel functionalization.

[0108] Stable solutions of nanogels in water were prepared by appropriately controlling both the redox state of the P(mDOPA) polymer and the pH of the PAH solution. The preparation conditions are crucial for the successful nanogel formation. First, P(mDOPA) is oxidized in aqueous medium under basic conditions for 12 h to form water-soluble Pox(mDOPA). The oxidized DOPA moiety of Pox(mDOPA) is necessary for the covalent interaction of PAHs via amine / quinone reaction and / or Schiff base formation at room temperature, and thus for the preparation of stable crosslinked nanogels (Figure 2).

[0109] The formation of nanogels Pox(mDOPA) / PAH was first performed by slowly adding a solution of PAH to an aqueous solution of Pox(mDOPA) at room temperature. The weight ratio and mode of addition of the two partners were controlled to form a stable dispersion of nanogels (Pox(mDOPA) / PAH). For that purpose, PAH was slowly added to an aqueous solution of Pox(mDOPA), resulting in the spontaneous formation of a stable, transparent, light brown solution of crosslinked nanogels at room temperature. The presence of nanogels was confirmed by transmission electron microscopy (TEM), performed after freeze-drying, which showed nanogels with diameters in the range of 100-200 nm (Figure 3b). It is important to note that the nanogel solution had to be freeze-dried on a TEM grid before analysis. When the solution was simply dropped onto the grid and slowly dried at room temperature under atmospheric conditions, the nanogels strongly aggregated (Figure 3a).

[0110] Analysis by dynamic light scattering (DLS) without filtration showed nanogel aggregates with a mean hydrodynamic diameter of 130 nm with a rather high polydispersity (PDI = 0.2) (Figure 4). The nanogel solutions were stable for at least one month when stored without stirring at room temperature and pH ~10. The solutions remained clear without precipitation, and the hydrodynamic diameter distribution obtained by DLS was almost unchanged after one month of storage.

[0111] The ability to load and deliver multiple drugs in the nanogels was further explored. Different bioactive agents were incorporated by a combination of covalent binding, electrostatic and hydrophobic interactions, and hydrogen bond formation. Covalent binding was performed by exploiting the reactivity of the quinone group of Pox(mDOPA) towards amine functional groups. For that purpose, vancomycin (V), a glycopeptide antibiotic containing a primary amine in its sequence, was used for conjugation, while physical entrapment was used for the incorporation of minocycline (M), an antibiotic of the tetracycline class, and ticagrelor (T), an antiplatelet agent with antithrombotic properties.

[0112] Pox(mDOPA)-VMT / PAH) was then prepared in a similar manner by adding a PAH solution to an aqueous solution of VMT-loaded Pox(mDOPA), resulting in the appearance of a yellow-brown suspension. DLS measurements without filtration evidenced the presence of nanogels with an average hydrodynamic diameter of 200 nm, slightly larger than the previous ones, probably due to the presence of VMT (bio)molecules (Figure 5).

[0113] The building block synthesis route is relevant for the development of environmentally friendly processes since all synthetic steps are carried out in aqueous media under mild conditions.

[0114] Oxidation of P(mDOPA) in basic medium: The oxidation was carried out according to a previous study (Faure et al., Biofouling. 2012:28(7):719-28). P(mDOPA) (20 mg) was dissolved in distilled water (20 mL) and NaOH solution (0.1 M) was slowly added to raise the pH to above 10. This oxidation step continued at least overnight under air.

[0115] The preparation of Pox(mDOPA) / PAH crosslinked nanogels was as follows. Preparation of nanogels: P(mDOPA) (2.5 mg) was dissolved in distilled water (5 mL) and NaOH (0.1 M) was slowly added to raise the pH above 10 and promote the oxidation of the catechol groups of P(mDOPA). After overnight at room temperature, a pH 10 PAH aqueous solution (0.5 mL; 0.5 g / L) was slowly added to the solution of Pox(mDOPA) under vigorous stirring. The solution was allowed to react for 1 h at room temperature under vigorous stirring. Nanogels with diameters ranging from 150 nm to 250 nm were observed by DLS.

[0116] Preparation of nanogel antibiotics (ABT): The procedure was identical to that described above, except that Pox(mDOPA) was solubilized in the presence of ABT (minocycline and vancomycin) to enhance the interaction between the polymer chains and the drugs. After 1 h at 6 °C, an aqueous solution of PAH (0.5 mL; 0.5 g / L) at pH 10 was slowly added to the solution of Pox(mDOPA) under vigorous stirring. The solution was allowed to react overnight at 6 °C under vigorous stirring, after which the nanogel was deposited. The final concentration of ABT in the nanogel solution was 0.5 mg / ml.

[0117] Preparation of nanogel tikageler (T): The procedure is identical to that described above, except that Pox(mDOPA) was solubilized in the presence of 1 ml of tikageler solution (1 mg / ml in DMSO) to enhance the interaction between the polymer chain and the drug. After 1 h at 6 ° C, an aqueous solution of PAH (0.5 mL; 0.5 g / L) at pH 10 was slowly added to the solution of Pox(mDOPA) / T under vigorous stirring. The solution was allowed to react overnight at 6 ° C under vigorous stirring, after which the nanogel was deposited.

[0118] Example 2 : Nanogel immobilization on titanium substrate using polydopamine coating The first strategy consisted of first immersing the substrate in a Tris-buffered solution of DOPA in order to strongly anchor the first layer to the surface by DOPA / metal interactions (Figure 6). The next layer was then constructed by successively immersing the surface in an aqueous solution of polyallylamine (PAH), a polymer with primary amines, and then in a solution of P(mDOPA)-based nanogels: poly(methacrylamide) with oxidized DOPA moieties on each monomer unit (Figure 1, formula (2)). Using Pox(mDOPA) in combination with PAH, a stable solution of nanogels in water at room temperature was prepared, which could be easily deposited on titanium (Ti) surfaces.

[0119] Polydopamine coating Polydopamine (PDOPA) has been used to modify biologically inert surfaces due to its ability to attach to a variety of material surfaces. The dopamine molecule has a 3,4-dihydroxy-L-phenylalanine-lysine motif, which can polymerize under mild conditions to form a PDOPA layer on the material surface. Incorporation of PDOPA as a primer film provides an alternative route to functionalize biomaterials with non-fouling surfaces, which can further enhance desirable biological, chemical, and therapeutic properties for biomedical applications.

[0120] Dopamine (2 mg / mL) was dissolved in 10 mM Tris-HCl (pH 8.5) and the substrate was immersed in the solution. The solution color changed to dark brown due to pH-induced oxidation and a thin adherent polymer film was deposited spontaneously (Figure 7). To avoid particulate deposition, a lower dopamine concentration of 0.125 mg / mL could be used and / or vertical sample orientation was required. The coated surfaces were rinsed with ultrapure water and dried with N2 gas before storage or treated as described below for ad-layer formation.

[0121] Polydopamine-assisted self-assembled PAH monolayers After modification of the titanium surface with PDOPA as the first layer, covalent grafting of PAHs occurs at room temperature via amine / quinone reactions and / or Schiff base formation, and thus for interlayer crosslinking (Scheme 1). Importantly, the next PAH solution was deposited at a pH above 10 to obtain the polymer in a deprotonated state. Therefore, the reaction between the primary amines and the quinone groups of Pox(mDOPA) was possible. In an acidic medium, crosslinking and growth of the film cannot occur, since the amine groups were protonated and did not react with Pox(mDOPA). For PAH adduct layer formation, a 1 mg / ml PAH solution was dissolved in ultrapure water and equilibrated at a pH above 10 by adding a 0.1 M NaOH solution. The polydopamine-coated substrate was then immersed in the solution. After more than 4 hours (typically 18 hours of reaction overnight), the substrate was rinsed with ultrapure water.

[0122] The contact angle of the dry titanium surface was measured after dropping 10 μL of ultrapure water. The static contact angles on the pure titanium and polydopamine-coated titanium surfaces were 85° ± 2° and 47 ± 6°, respectively, proving the modification of the surface.

[0123] Nanogel Assembly Covalent grafting of nanogels was performed through the same reaction and / or Schiff base formation between the primary amines of the PAH monolayer in the nanogel and the quinone groups of Pox(mDOPA). The surfaces coated with a layer of PDOPA and a layer of PAH were then incubated with an aqueous solution of nanogel Pox(mDOPA) / PAH according to the protocol described below. Contact angles were measured on titanium surfaces modified with PAH and nanogel. The contact angle of PAH was about 65°. Its amplitude was larger than that measured on polydopamine-coated surfaces, probably due to the presence of apolar amine groups. After deposition of nanogels, which exhibit the same catechol groups as polydopamine, the contact angle decreased to about 42°.

[0124] PEG-grafted monolayer Poly(ethylene glycol) (PEG) is one of the most commonly used synthetic polymers to confer protein resistance to surfaces. Several strategies for modifying substrates with that kind of polymer can be found in the literature, such as electrografting, self-assembled monolayers (SAMs), and copolymer adsorption, to name just a few. PEG grafting was performed by exploiting the reactivity of the quinone group of Pox(mDOPA) towards thiols. For that purpose, thiol-terminated functionalized PEG (PEG-SH) was considered for conjugation. This thiol-based strategy allows specific grafting in mild conditions and without pH limitations, in contrast to amino-based strategies that require a pH ≥ 10. For PEG grafting, 5 mg / mL of methoxy-poly(ethylene glycol)-thiol (mPEG-SH, 1.5 kDa) was dissolved in 10 mM Tris pH 8.0. The buffer used for mPEG-SH was vacuum degassed for about 1 h to prevent oxidation (-SS-) between thiol groups. PEG was reacted to the PDOPA layer (nanogel layer) via Michael-type addition and Schiff base reaction to suppress nonspecific interactions and increase hydrophilicity under physiological conditions. Water contact angles verified the anchoring of PEO chains to the modified Ti surface. Surprisingly, a PEO layer exhibiting a contact angle of 43°±1 was found.

[0125] Briefly, nanogel deposition with PDOPA as the first layer was carried out in five steps at room temperature. Step 1: Ti disks (1 cm diameter) were sonicated in tetrahydrofuran (THF), acetone, ethanol, and water for 10 min for each step. Step 2: Ti was immediately added to DOPA Tris buffer (0.125 g / L - 1 ) for 18 hours. Step 3: After rinsing twice with 5 ml of water, the modified substrate was immersed in a solution of PAHs (pH>10) for 18 h and then rinsed twice with 5 ml of water. Step 4: After rinsing twice with 5 ml of water, the modified substrate was immersed in the solution of nanogels (loaded with ABT and T) for 18 h and then rinsed twice with 5 ml of water. Step 5: After rinsing twice with 5 ml of water, the modified substrate was immersed in a solution of PEG-SH for 1 hour and rinsed twice with 5 ml of water.

[0126] Surface morphology is an important parameter for biomedical devices that can affect the interfacial energy and even the interaction between biological components and the material surface. To gain further information and understand the microstructure of the nanogel-coated Ti surface, field emission scanning electron microscopy (SEM) observations were performed (Figure 8). The pristine Ti surface exhibited a relatively smooth morphology (left panel). In contrast, after nanogel deposition, numerous well-dispersed nanogels with sizes ranging from 80 nm to 120 nm were observed (right panel). The results showed that the size of the deposited nanogels corroborated the size of the nanogels measured by TEM in solution (Figure 2b).

[0127] Layer-by-layer (LbL) assembly LbL deposition was performed under the same conditions using a similar procedure as above, except that steps 2 to 4 were repeated five times to obtain five layers.

[0128] Quartz Crystal Microbalance As a first evidence of multilayer film formation, a quartz crystal microbalance coupled with dissipation (QCM-D) was used to track film growth in real time on a gold sensor by measuring the variation of the resonant frequency (Δf) versus time. A decrease in Δf indicates polymer deposition. Figure 9 shows that all components were successfully deposited according to the selected deposition protocol and redox / pH conditions and remain on the substrate even after rinsing with water.

[0129] First, DOPA (0.125 g / L) in Tris buffer was flowed through the cell at room temperature to obtain the first immobilized layer. The f-shift continued to decrease until DOPA was washed out of the sample chamber. Second, a negative shift was observed immediately upon injection of the PAH solution (pH > 10), indicating an increase in mass at the interface as the polymer adsorbs onto the gold surface. After rinsing with water to remove excess unbound polymer, a stable baseline was achieved during the rinsing step, demonstrating that the polymer adduct layer was strongly tethered onto the surface. After the reversibly adsorbed polymer was removed by the rinsing step, a nanogel solution in Milli-Q water (pH ~10) was introduced into the sensor chamber at the same flow rate and temperature. The deposition of the nanogel solution was observed by a significant decrease in the frequency oscillations. Importantly, this nanogel layer was stable as it could not be removed after rinsing with water. In the last step, irreversibly attached polymers can be seen from the raw Δf after injection of the PEG-SH solution due to the reaction of thiol functional groups with residual quinone groups present in the nanogel (Figure 9).

[0130] Example 3 : Direct nanogel immobilization on titanium substrate In the second approach, the titanium surface was directly immersed in the nanogel solution to obtain a nanogel-modified surface without the need for a primer coating. In this case, the assembly mechanism is based on the adhesive properties of the catechol and quinone groups present on the surface of the nanogel (Figure 10).

[0131] Using SEM analysis, the formation of a monolayer of nanogel Pox(mDOPA) / PAH on Ti was observed (Figure 11). The estimated diameter of the nanogels was found to vary between 80 nm and 120 nm.

[0132] Example 4 Immobilization of nanogels on valve bioprostheses The same approach as reported above was used to modify biological valves. Considering the same process, the biological valves were first immersed in a Tris buffer of DOPA (10 mM Tris-HCl (pH 8.5)) to strongly immobilize the first layer of polydopamine. As a result of the deposition of a thin, adherent PDOPA film, the implants turned dark brown (Figure 12).

[0133] The next layer was then constructed by successively immersing the valve in an aqueous solution of polyallylamine (PAH) and then in a solution of P(mDOPA)-based nanogel.

[0134] The following steps were carried out at room temperature. Step 1: A biological disc (1 cm diameter) was immersed in 10 ml of water for 10 min three times. Step 2: Immediately soak the biological disc in DOPA Tris buffer (0.125 g / L - 1 ) for 18 hours. Step 3: After rinsing twice with 5 ml of water, the modified tissue was immersed in a solution of PAHs (pH>10) for 18 h and rinsed twice with 5 ml of water. Step 4: After rinsing twice with 5 ml of water, the modified tissue was immersed in the solution of nanogel for 18 h and then rinsed twice with 5 ml of water. Step 5: After rinsing twice with 5 ml of water, the modified tissue was immersed in a solution of PEG-SH for 1 hour and rinsed twice with 5 ml of water.

[0135] Scanning electron microscopy (SEM) was used to analyze the surface morphology of the modified biological tissue. It was observed that the surface of the biological tissue before modification exhibited relatively smooth and ordered collagen nanofibers. After nanogel deposition, the collagen fibers appeared more compact (Figure 13), and well-dispersed nanogel was observed on the surface of the collagen fibers (Figure 14). The PDOPA primer coating enhanced nanogel deposition.

[0136] A quartz crystal microbalance coupled with a dissipation technique (QCM-D) was used to track the film growth (PDOPA and nanogel) in real time. A Q-Sense E4 was used in this study. A stainless steel coated AT-cut resonator (fundamental frequency 5 MHz) was used as is. First, distilled water was introduced into the cell and the flow was maintained until a stable baseline was obtained. The liquid exposed to the crystallograph was then changed from distilled water to a 0.125 g / L DOPA solution containing 0.15 M NaCl. -1 Flow rate: 200 μL / min -1 The LbL deposition was started by switching the temperature at 25 °C. After 10 min, the substrate was rinsed with distilled water to remove excess unbound DOPA. PAH (1 g L) was then added, with a rinse step with distilled water between each layer. -1 ) and nanogel solution were then alternately deposited (~10 min for each step). Finally, the PEG-SH solution was introduced into the system as the final layer and further rinsed when a stable signal was obtained.

[0137] The hydrodynamic diameter of the aqueous nanogel solutions was measured using a Delsa Nano-C Particle Analyser (Beckman Coulter) equipped with a laser diode source (wavelength 658 nm; power 30 mW). Scattering data were collected for at least 50 individual measurements at a constant scattering angle and averaged for each sample. The resulting scattering data were fitted using volume-weighted cumulative analysis to estimate the diffusion coefficient of the nanogel in the solution. The hydrodynamic diameter (DH) of the samples was obtained using the Stokes-Einstein relationship:

[0138] Specimens for scanning electron microscopy (SEM) were analyzed after a thin layer (10 nm) of Au-Pd to enhance the contrast. A field emission gun scanning electron microscope (FEG-SEM) MEB ULTRA55 operated at 3 kV was used to observe the specimens.

[0139] Synthesis of N-methacryloyl 3,4-dihydroxy-L-phenylalanine methyl ester DOPA methyl ester hydrochloride (9 g, 0.0363 mol) in dry CHCl (350 mL) was added to a two-necked round-bottom flask equipped with a dropping funnel and a magnetic stirrer and placed under nitrogen. Freshly distilled EtN (17.7 mL, 0.127 mol) was then added and the flask was cooled to 0 °C. A solution of methacryloyl chloride (3.51 mL, 0.0363 mol) in CHCl (70 mL) was added dropwise through the dropping funnel with vigorous stirring under nitrogen. The final mixture was kept stirring at room temperature for 48 h. After the reaction, triethylammonium chloride formed as a by-product was removed by filtration and excess reagents were removed under reduced pressure. The product was recovered as a sticky solid in 90% yield.

[0140] P(mDOPA) synthesis Prior to polymerization, the catechol group of mDOPA must be protected from its -OH group to avoid side reactions during radical polymerization. 2 g of mDOPA with a protected catechol group (see below for protection step) (2.6 mmol) was placed under nitrogen in a one-neck round-bottom flask equipped with a magnetic stirrer. At the same time, 19 mg (0.067 mmol) of V501 initiator was dissolved in 7 mL of distilled water. The pH solution was adjusted with NaCl until the white powder was completely dissolved. 2 CO 3 The pH was adjusted above 9 with 500 mM NaOH. The solution was then degassed by bubbling nitrogen through it for 15 minutes. The aqueous solution of V501 initiator was then transferred using a capillary under nitrogen into the glass flask containing the protected mDOPA. The reactor was heated in an oil bath thermostated at 70° C. for 24 hours. The catechol group was then deprotected by adjusting the pH to about 2 with concentrated HCl. The resulting mixture was dialyzed against water for 48 hours (membrane porosity 1000 Da) and subsequently lyophilized. The copolymer was recovered as a white powder in 88% yield.

[0141] Synthesis of α-methoxy-ω-mercapto-poly(ethylene oxide) (MPEG-SH) α-Methoxy-x-mercapto-poly(ethylene oxide) (MPEG-SH) was synthesized by esterification of the hydroxyl end groups of monomethoxypoly(ethylene oxide) (MPEG-OH) (Mn=1500 g / mol) with mercaptoacetic acid. A typical reaction was carried out as follows: MPEG-OH (10 g, 5 mmol) was added to a 100 ml two-neck flask equipped with a stirrer and a Dean-Stark apparatus. MPEG-OH was dried by azeotropic distillation with toluene three times and finally dissolved in 50 ml of toluene. Mercaptoacetic acid (3.5 ml, 50 mmol) and concentrated sulfuric acid (2 drops) were then added. The flask was heated at 110 °C in an oil bath overnight. MPEG-SH was collected by precipitation in ether at 0 °C and then dried in vacuum at 40 °C for 24 h.

[0142] Example 5 : Antithrombotic properties of bioactive nanogels Dynamic Impact-R Test To study blood-material interactions in dynamic conditions, the Impact-R device was used. It is a physiologically close in vivo system that mimics the laminar flow of blood in circulation and is used to study platelet function and thrombus formation under blood flow. The laminar flow, generated by rotating a piston (bell and cone) at a constant speed on a thin layer of blood deposited on a well, activates platelets by shear stress, which adhere to the polystyrene surface of the well and are then stained with May-Grünwald stain. The system allows for a change in speed, and the faster the speed (corresponding to a faster heart rate), the more thrombus forms on the surface.

[0143] Examination of the polystyrene surfaces under an optical microscope and image analysis determined the percentage of the surface covered with platelet aggregates (SC, %) and the average size of the aggregates (thrombi) (AS, μm 2 ) two parameters can be obtained.

[0144] Tests were performed with citrated blood from healthy donors. The SC and AS obtained were proportional to the speed rotation of the cone at a particular well radius (speed increases with radius).

[0145] The effect of different polymer coatings at different time points was tested (Figure 15). Polymers (PEG and reticulated PEG, APEG) were covalently attached to a thin polydopamine layer DOPA (also tested alone) and had a small, but not significant, effect on reducing platelet activation and adhesion. Increasing the time of shear stress applied to the blood significantly increased the two parameters SC and AS. For both SC and AS parameters, significant differences were found between the uncoated (NC) and PEG-coated surfaces at all time points.

[0146] Next, three healthy donors were subjected to in vitro shear stress of 1800 s for 2 min on the Impact-R. -1 Using , polydopamine (DOPA), DOPA-PEG (PEG), DOPA-nanogel (NGEL) and DOPA-nanogel-PEG (NGEL-PEG) coatings were tested (Figure 16A, Figure 16B). With the exception of DOPA, significant differences in SC values ​​were observed for all coatings compared to NC. PEG-coated PS wells produced the lowest SC and AS values. Platelets were unable to form aggregates on the PEG-coated surface. Importantly, the nanogel deposition did not exhibit platelet adhesion properties.

[0147] The test in FIG. 17 was carried out to study the effect of ticagrelor alone (NG-T-PEG) or in combination with two antibiotics (NG-TA-PEG) on flow-induced platelet consumption. The test was carried out on a blood sample from one donor for 1800 seconds. -1 The nanogels were incubated at 4°C for 4 min. No platelet binding was observed in any condition except in the non-coated (NC) wells. The values ​​reported in Figure 17 represent the number of single platelets in the blood after the test and therefore represent platelet aggregate formation on the surface and / or in the blood. A significant increase in platelet count was observed for both nanogels, indicating that the platelets remained suspended as single platelets (i.e., were not activated) and did not adhere to the surface.

[0148] Static Testing The hemocompatibility of the coating was investigated under static conditions (no applied shear stress). Static tests were performed by adding 500 μL of fresh blood to a 24-well untreated plate at 37 °C and 5% CO. 2 The results were analyzed by incubating at 4°C for 2 h with gentle agitation (60 rpm) and observing cell attachment by optical microscopy in the presence or absence of coating. Crystal violet dye was used to stain the cells. In Figure 18, optical microscopy images of cells stained with crystal violet highlight the inhibition of hemocyte attachment after PS surface modification. The conditions were: non-coated (NC), nanogel (NG), nanogel Peg (NP) and nanogel antibiotic Peg bound to a polydopamine layer (NAP).

[0149] Platelet suspensions (PRP: platelet rich plasma) were also incubated with NAP-coated PS wells for 1 min (Figure 19A) or 45 min (Figure 19B). Clear differences in surface coverage were observed compared to NC-PS wells. NC-1 min had 90% surface coverage (SC), NAP-1 min had 5% SC, NC-45 min had 99.5% SC, and NAP-45 min had 40% SC.

[0150] Thus, all these data indicate that surface modification with the nanogel preparation of the present invention does not activate platelets under static and dynamic conditions.

[0151] Example 6 : Anti-biofilm properties of bioactive nanogels: Staphylococcus aureus Staphylococcus aureus biofilms grown for 24 h in 24-well plates under static conditions were analyzed by crystal violet staining (Figure 20). A reduction in biofilm was observed when nanogels were loaded with minocycline. In contrast, covalently bound vancomycin does not reduce biofilm formation. Thus, the Ng-Mino-Peg condition resulted in a 95% reduction in planktonic bacteria compared to all other conditions.

[0152] In the case of biological valve discs incubated with S. aureus in 24-well plates under static conditions for 24 h, planktonic bacteria were completely killed when incubated with Ng-ABsPeg-modified discs, whereas viable bacteria were present in the uncoated disc condition.

[0153] Interestingly, SEM analysis of the biological valve surface modified with vancomycin, minocycline, and ticagrelor loaded nanogels did not detect any bacteria, whereas the unmodified surface revealed abundant biofilm (Figure 21). Thus, the bioactive nanogels of the present invention confer strong anti-biofilm properties to biological valves.

[0154] Example 8 : Anti-biofilm properties of bioactive nanogels: Yersinia faecalis Figure 22 shows the effect of PS surface modification on biofilm formation of L. faecalis. Antibacterial activity was observed by assessing the viability of the bacteria in suspension. Vancomycin-loaded nanogels exhibited antibacterial activity under static conditions, demonstrating that the covalent attachment of the antibiotic in the nanogels preserved its activity. Minocycline was effective under both shaking and static conditions.

[0155] Example 9 Defining the optimal ratio of minocycline and ticagrelor to create nanoreservoirs with antithrombotic properties To produce nanoreservoirs with both antibacterial and antiplatelet activity that would exhibit optimal antithrombotic properties, the optimal concentration of the antiplatelet drug ticagrelor was first determined. For this purpose, 1 ml of nanogel suspension loaded with increasing concentrations of ticagrelor was centrifuged at 12000 g for 15 min, washed twice in PBS, and resuspended in 300 μL of PBS. 260 μL of platelet-rich plasma (PRP) was incubated with 10 μL of purified nanogel suspension for 10 min. Platelet aggregation was then induced by adding 10 μM ADP at 37 °C under stirring conditions. The potency of the nanogel suspension to inhibit ADP-induced platelet aggregation was compared to that of the IC50 concentration of free ticagrelor. It was observed that nanogels loaded with 112 μg / mL of ticagrelor inhibited platelet aggregation as potently as 1.8 μg / mL of ticagrelor (Figure 23A). This loading concentration was used for subsequent studies.

[0156] It was confirmed that antiplatelet nanogels (loaded with 112 μg / mL ticagrelor) were more readily formed in the absence of minocycline. Therefore, to obtain nanoreservoirs containing minocycline and ticagrelor, a strategy was adopted in which two nanogel solutions were mixed in an x / y ratio. Ratios of x (minocycline) / y (ticagrelor) between 1 / 5 and 2 / 3 provided optimal inhibition of ADP-induced platelet aggregation (Figure 23B). Furthermore, immobilization of the nanogel mixture prepared in a 2 / 3 ratio on a polystyrene surface did not activate the coagulation of human plasma compared to a non-coated surface (Figure 24).

[0157] Example 10 : Multilayer assembly of nanogels improves the antibiofilm and antithrombotic efficacy of nanoreservoirs We next evaluated whether multilayer assemblies could improve the antibacterial and antiplatelet efficacy of the nanoreservoirs. One, three, or five layers of nanogels were immobilized on polystyrene or titanium surfaces. The surfaces were then incubated with S. aureus, and biofilm formation was quantified as described in Methods. Increasing the number of nanogel layers was found to enhance the nanoreservoir antibiofilm effect (Figure 25).

[0158] To study the antiplatelet effect of the immobilized multilayered nanoreservoirs, a test was set up with the Impact R instrument (see Methods). Whole blood was preactivated with 2.8 μM ADP for 1 min at room temperature under gentle stirring or without, followed by 4 min of rotation at 720 rpm. Surface coverage and aggregate size were determined for each test surface, and the reduction in platelet count was analyzed in the supernatant. It was expected that ticagrelor released from the nanoreservoirs would be able to reverse the ADP effect, since it has a higher affinity for the platelet P2Y12 receptor.

[0159] The effect of one-layer ticagrelor / minocycline-loaded nanogels was compared with five-layer loaded nanogels (Figure 26). Non-coated and non-loaded nanogel-coated surfaces were also included. Preactivation with ADP induced the formation of microaggregates in solution, which led to a decrease in surface coverage (Figure 26A) and a slight increase in aggregate size (Figure 26B), translating into the loss of single platelets (Figure 26C) when compared to non-activated blood incubated on non-coated (NC) or non-loaded nanogel (NG)-coated surfaces. Blood incubation on loaded nanogel-coated surfaces inhibited the effect of ADP as a result of ticagrelor release from the nanoreservoirs. The efficacy of the five-layer nanoreservoirs was superior to that of the one-layer ones in terms of surface coverage and aggregate size. Both nanoreservoirs restored the ADP-induced loss of single platelets in solution.

[0160] Example 11 : Reticulation of multilayer nanogel assemblies delays release and extends efficacy of bioactive molecules The release of bioactive molecules was observed to be slowed down by reticulating the five-layer nanogel assemblies with dopamine in the final step of nanoreservoir formation. By adjusting the crosslinking density of the nanogel coating, the diffusion rate of the loaded molecules can indeed be tuned. Dopamine acts as a crosslinking agent to slow down the diffusion of bioactive molecules from the nanoreservoirs. This dopamine treatment can affect the diffusion of molecules in two different ways. First, dopamine can penetrate within the different layers of the LBL nanogel assemblies and react with the nanogel, thereby increasing its crosslinking density. Second, dopamine can polymerize in solution and deposit by precipitation as a thin layer on the surface of the LBL, acting as an additional barrier to the diffusion of bioactive molecules.

[0161] After the deposition steps of the different layers, the resulting LBL assemblies were immersed in a 0.125 mg / ml dopamine solution for 1 h. After washing the surfaces, PEG1500 was grafted onto them. The coated and uncoated surfaces were incubated in medium alone for 48 h. After two medium changes, bacteria were allowed to attach as described above. Figure 27A shows that non-reticulated nanoreservoirs (NTMV) loaded with minocycline and vancomycin failed to inhibit S. aureus biofilm formation, whereas the reticulated nanoreservoirs (D-NTMV) were still active after 48 h. Figure 27B shows the antibacterial effect of the medium removed after a second 24 h of contact with the two types of nanoreservoirs, demonstrating the release of higher concentrations of antibiotics from the reticulated nanoreservoirs during this contact period.

[0162] Example 12 : In vivo demonstration of antibacterial efficacy of nanoreservoirs immobilized on Ti implants To demonstrate the anti-biofilm efficacy of the nanoreservoirs in vivo, a mouse model of titanium implant S. aureus infection was used. Pre-infected titanium devices were implanted subcutaneously and in vivo biofilm formation was assessed after 4 hours. Figure 28A shows the number of CFU per explanted titanium disc after correcting for the initial CFU per disc at the time of implantation. The nanoreservoirs completely prevented biofilm formation on the titanium implants compared to unloaded nanogel. This result was further confirmed by scanning electron microscopy of the titanium implants (Figure 28B). Bacteria were seen on titanium coated with unloaded nanogel only. Immune cells were observed on the nanoreservoir-coated implants.

[0163] Example 13 : Preparation of Layer-by-Layer Assembled Crosslinked Nanogels Coated with Different Thiol or Vinyl End-Functionalized Ligands To identify nanogel formulations that would exert unique anti-adhesive properties against platelets and bacteria, different thiol- or vinyl-end-functionalized ligands were added as the final layer of the LBL-assembled nanogels.

[0164] α-Methoxy-ω-mercapto-poly(ethylene oxide) (MPEG-SH), designated PEG1.5, was synthesized by esterification of the hydroxyl end groups of monomethoxypoly(ethylene oxide) (MPEG-OH) with mercaptoacetic acid as follows (Mn = 1500 g / mol). [ka] MPEG-OH (10 g, 5 mmol) was added to a 100 ml two-neck flask equipped with a stirrer and a Dean-Stark apparatus. MPEG-OH was dried by azeotropic distillation with toluene three times and finally dissolved in 50 ml of toluene. Mercaptoacetic acid (3.5 ml, 50 mmol) and concentrated sulfuric acid (2 drops) were then added. The flask was heated at 110° C. in an oil bath overnight. MPEG-SH was collected by precipitation in ether at 0° C. and then dried in vacuum at 40° C. for 24 hours. PEG-SH was characterized by 1H NMR (FIG. 29).

[0165] PEG2 (methoxy-PEG-(CH2)2-SH, Mw 2,000, chemical name: α-mercaptoethyl-ω-methoxy, polyoxyethylene, reference symbol SUNBRIGHT® ME-020SH), PEG5 (methoxy-PEG-(CH2)2-SH), Mw 5,000, chemical name: α-mercaptoethyl-ω-methoxy, polyoxyethylene, reference symbol SUNBRIGHT® ME-050SH), and PEG10 (methoxy-PEG-(CH2)2-SH, Mn 10,000, chemical name: α-mercaptoethyl-ω-methoxy, polyoxyethylene, reference symbol SUNBRIGHT® ME-100SH) were obtained from NOF corporation.

[0166] The chemical formula of MPEG-SH from NOF corporation is as follows: [ka]

[0167] The vinyl end functionalized PEG ligands (PEG-acrylates) used were polyethylene glycol methyl ether acrylate, Mn 480, Sigma-Aldrich, reference 454990 (APEG0.5), and polyethylene glycol methyl ether acrylate, Mn 1,000, Alfa Aezar. reference 46537 (APEG1). Their chemical formulas are as follows: [ka] The synthesis method of polybetaine is shown below. Polymerization of 2-(methacryloyloxy)ethyl phosphorylcholine (MPC) was achieved by adding MPC (0.5 g, 1.7 mmol), 4-cyanopentanoic acid dithiobenzoate (CTP; 10 mg, 0.05 mmol), AIBN (1.2 mg, 7.3×10-3 mmol), and deionized H2O:MeOH 3:1 (5.0 ml) in a Schlenk flask equipped with a magnetic stir bar. The mixture was then stirred in an ice bath to completely dissolve the CTP and AIBN. The solution was then purged with nitrogen and then immersed in a preheated oil bath at 70 °C. After 12 h, polymerization was stopped by rapid cooling and exposure to air. The polymerization solution was then dialyzed against deionized water for 12 h with three changes of deionized water. The homopolymer was then recovered by lyophilization. Polybetaine was characterized by 1H NMR (Figure 30). [ka]

[0168] Stable solutions of nanogels in water were prepared by appropriately controlling both the redox state of the P(mDOPA) polymer and the pH of the PAH solution. First, P(mDOPA) is oxidized in aqueous medium under basic conditions for 12 h to form water-soluble Pox(mDOPA). The oxidized DOPA moiety of Pox(mDOPA) is necessary for covalent interaction of PAHs via amine / quinone reaction and / or Schiff base formation at room temperature, and thus for the preparation of stable crosslinked nanogels.

[0169] Immobilization of the crosslinked nanogels on the surface of the substrate was achieved by first dipping / immersing the substrate in a Tris buffer solution of DOPA to strongly anchor the first layer to the surface. The next layer is then built up by successively immersing the surface in an aqueous solution of polyallylamine (PAH), a polymer with primary amines, and a solution of the nanogel, followed by washing twice with deionized water. A layer-by-layer (LBL) assembly was obtained by repeating the above deposition and washing steps. Then, solutions of thiol and vinyl end-functionalized ligands (5 mg / ml in 10 mM Tris pH 8.0) were added as the final layer by exploiting the reactivity of the quinone group of Pox (mDOPA) towards thiols, and through Michael-type addition and Schiff base reaction with the amine groups of PAH, respectively.

[0170] The table below shows the contact angles measured on nanogel coated surfaces with different ligands with thiol or vinyl functionalized ends compared to polydopamine.

[0171] [Table 1]

[0172] In the following examples, the anti-adhesion (plasma proteins, platelets and bacteria) properties of surface-immobilized five-layer nanogels grafted with different ligands as the final layer were tested. The effect on activation of the contact phase of coagulation was also studied.

[0173] Example 14 Ligands with thiol-functionalized ends are superior to ligands with vinyl-functionalized ends in preventing platelet adhesion to immobilized nanoreservoirs To compare platelet adhesion on polystyrene surfaces coated or uncoated with 5-layer nanogels or nanoreservoirs with a top layer of PEG containing thiol or vinyl functionalized ends, an LDH activity assay was performed (Figure 31). After 45 min of incubation of PRP on the surface, nanoreservoirs made with minocycline and ticagrelor loaded PEG-SH nanogels (ratio 2 / 3, see above) efficiently inhibited platelet adhesion compared to unloaded nanogels, whereas the same nanoreservoirs made with nanogels bearing PEG-acrylate were less efficient.

[0174] Example 15 Advantages of PEG2000 ligands with thiol-functionalized termini for preventing Staphylococcus aureus biofilm formation on nanogel-coated titanium implants To determine whether ligand grafting onto nanogels can confer anti-adhesive properties to surfaces by itself, we compared S. aureus biofilm formation on medical grade titanium implants that were coated or not with five-layer nanogels bearing different ligands containing thiol or vinyl functionalized ends. Biofilm formation was assessed by isolating and plating the attached bacteria after 3 hours on the implants. CFU counts were then determined. The thiol-terminated PEG2000 ligand appeared to confer the most efficient anti-biofilm properties to titanium compared to polybetaine 15000 and PEG-acrylate 500 and 1000 (Figure 32).

[0175] Example 16 PEG ligands with thiol-functionalized termini: Effect of molecular weight on bacterial adhesion Further comparison was made of the S. aureus anti-biofilm efficacy of nanogels with PEG thiols of molecular weight above 2000. Figure 33 shows that the anti-biofilm efficacy of PEG thiol-nanogels increases with PEG molecular weight.

[0176] Example 17 PEG ligands with thiol-functionalized termini: Effect of molecular weight on platelet adhesion under flow With the aim of creating a surface with both anti-biofilm and anti-platelet properties, experiments on platelet adhesion under flow were performed using the Impact-R system, comparing the same PEG thiol ligands as in Example 16 (Figure 34). In contrast to biofilm formation, the results show that nanogels without grafted polymers already confer an anti-platelet effect on the surface, as shown by the lower percentage of surface coverage by platelets compared to the uncoated surface, and by the smaller aggregate size. Differences were also observed between the anti-biofilm and anti-platelet effects with regard to the PEG thiol molecular weight. Indeed, optimal anti-platelet coverage was achieved by using PEG1500 or PEG2000, while increasing the molecular weight did not improve the effect.

[0177] Example 18 PEG ligands with thiol-functionalized termini: Effect of molecular weight on coagulation The clotting times of plasma in contact with coated and non-coated surfaces were compared. The reference was plasma in basal state, i.e. plasma not in contact with any surface (except the surface of the tube and the chip) (Figure 35). Figure 35 shows the shortening of clotting times obtained when negatively charged kaolin is immobilized on the surface, and the opposite effect of the FXIIa inhibitor CTI. It was observed that the surfaces coated with 5-layer nanogels with PEG ligands slightly prolonged the clotting time compared to the non-coated surfaces. Comparing PEGs of different molecular weights, it was observed that the longest clotting times were produced by nanogels with PEG 2000 and 5000. Thus, although a complete inhibition of the contact phase of clotting was not reached, these nanogels were able to improve the effect of non-coated surfaces.

[0178] Example 19 : PEG thiol ligands are superior to polybetaine in preventing biofilm formation The data presented here show that grafting of PEG2000 onto nanogel assemblies can confer anti-adhesion to surfaces for both platelets and bacteria. Polybetaines of different chain sizes and molecular weights were further compared using PEG2000 as a reference. Biofilm formation was first evaluated using the IVIS Lumina system and bioluminescent Staphylococcus aureus (Figure 36). This technique allowed tracking the kinetics of bacterial attachment to the test surface. As shown in Figure 36, PEG2000 remained the best anti-biofilm ligand among all polybetaines tested.

[0179] Example 20 : PEG thiol ligands are superior to polybetaine in preventing platelet adhesion under flow conditions Similar to above, the efficacy of polybetaine ligands of different chain sizes and molecular weights to prevent platelet adhesion under flow conditions was evaluated (Figure 37). It was observed that PEG2000 was superior to either polybetaine in terms of surface coverage and size of platelet aggregates formed on the surface. In contrast, no differences were observed between thiol-terminated PEG and polybetaine when evaluating platelet adhesion under static conditions (Figure 38).

[0180] Example 21 : PEG ligands with thiol-functionalized ends are superior to polybetaine in terms of coagulation Of the thiol-terminated PEG ligands, PEG2000 was shown to produce the lowest coagulation activation (Figure 35). PEG2000 with thiol-terminated polybetaines of increasing chain size and molecular weight was also compared. Figure 39 does not show the effect of chain size on the polybetaine polymer, but it was confirmed that PEG2000 did not produce more contact phase activation than basal plasma not in contact with the surface of the PS well.

[0181] Example 22 : PEG ligands with thiol-functionalized termini are superior to polybetaine in preventing plasma protein adhesion When plasma or blood comes into contact with a foreign surface, the first event is protein adsorption, which promotes platelet adhesion and leads to activation of the intrinsic cascade of coagulation. Therefore, testing for plasma protein adhesion is a critical step in the development of hemocompatible devices.

[0182] The surface of a polystyrene well was coated or uncoated with a 5-layer nanogel with or without different molecular weights of PEG or polybetaine as the final top layer. This study is consistent with the general idea that the length of the grafted polymer can prevent nonspecific adsorption of proteins. Our results show that PEG2000 (NG-P2) and 5000 (NG-P5) improve the antifouling properties of the surface compared to nanogels without grafted polymers (NG), but polybetaine (NG-PB7, 15, 44) cannot (Figure 40).

[0183] It will be understood that references to nanogels in the examples can also be replaced with references to nanoreservoirs. The reader will understand that the term nanogel can be used to refer to nanoreservoirs that contain nanoparticles made from nanogels.

[0184] Other embodiments are intended to be within the scope of the present invention as defined by the following claims.

Claims

1. 1. A biomaterial implant, medical device or bioprosthesis having a surface or a portion thereof coated with a network of nanoreservoirs of a multi-layered nanogel assembly comprising two or more layers of nanogel nanoparticles, said nanogel comprising an oxidized form of P(mDOPA), said oxidized form of P(mDOPA) being crosslinked to a PAH via a quinone-amine reaction; the reticulated nanoreservoirs further comprise one or more bioactive molecules, therapeutic molecules, or drugs that are continuously released from within the reticulated nanoreservoirs; The layers may be the same or different, the differences in the layers being due to differences in the bioactive molecules, therapeutic molecules or drugs; The oxidized form of P(mDOPA) is the polymer Pox(mDOPA) having the following monomer units: 【Chemistry 1】 Biomaterial implants, medical devices or bioprostheses.

2. The biomaterial implant, medical device or bioprosthesis of claim 1 , wherein the reticulated nanoreservoirs contain an antibiotic and / or an antiplatelet agent.

3. The biomaterial implant, medical device or bioprosthesis according to claim 1 or 2, wherein said nanoparticles have a diameter of between 100 nm and 250 nm.

4. The biomaterial implant, medical device or bioprosthesis of any of claims 1 to 3, wherein at least some of said nanoparticles are decorated with hydrophilic functionalized ligands, said hydrophilic functionalized ligands being thiol or vinyl end-functionalized ligands.

5. 5. The biomaterial implant, medical device or bioprosthesis of claim 4, wherein the hydrophilic functionalizing ligand is PEG2 or a PEG having a molecular weight greater than 2000.

6. The bioprosthesis of any one of claims 1 to 5, wherein the bioprosthesis is a heart valve or a catheter.

7. 1. A method for producing a medical device, biomaterial implant or bioprosthesis having a coated surface, comprising: i) immersing the surface to be coated in a solution of P(mDOPA); ii) oxidizing said P(mDOPA) to obtain Pox(mDOPA) to obtain a surface having one or more quinone moieties; iii) immersing the surface obtained in step ii) in a solution of PAHs; iv) immersing the surface resulting from step iii) in a nanoreservoir solution containing nanoparticles of nanogel to produce a coating on said surface, said nanogel containing said Pox(mDOPA) crosslinked to said PAH via a quinone-amine reaction; repeating steps iii) and iv) to obtain a reticulated nanoreservoir of multi-layered nanogel assemblies containing two or more layers of nanoparticles; A method comprising: the nanoparticles comprise a bioactive molecule, a therapeutic molecule or a drug; The layers may be the same or different, the differences in the layers being due to differences in the bioactive molecules, therapeutic molecules or drugs; The Pox(mDOPA) is a polymer having the following monomer units: 【Chemistry 2】 The reticulated nanoreservoirs allow one or more bioactive molecules, therapeutic molecules, or drugs to be released continuously from within the reticulated nanoreservoirs; method.

8. 8. The method of claim 7, further comprising the step of: v) immersing the coated surface of step iv) in a solution of a hydrophilic functionalizing ligand, the hydrophilic functionalized ligand is a thiol or vinyl end-functionalized ligand; method.

9. 9. The method of claim 8, wherein the hydrophilic functionalized ligand is PEG2 or a PEG having a MW greater than 2000.

10. The method according to any of claims 7 to 9, wherein the nanogel of step iv) comprises an antibacterial and / or anti-platelet agent.

Citation Information

Patent Citations

  • Antimicrobial coating for inhibition of bacterial adhesion and biofilm formation

    JP2013032530A